Mechanical property of red mud-slag-fly ash based alkali-activated mortar with recycled waste glass aggregate - Ting-Ting Tang; Lan-Ping Qian; Hai-Tao Wang; Dong Guo; Kai-Di Peng; Jun-Qi Huang (European Journal of Environmental and Civil Engineering, 2026)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

Improving variant interpretation and diagnosis in Koolen-de Vries syndrome through a curated genotype–phenotype repository - Hailin Huang; Jia Geng; Yang Long; Wenyu Xiong; Xiaolu Wang; Chao Wang; Qian Zhang; Ting Tang; Yuxin Chen; Yu Zhao; Jing Cheng; Yu Lu; et al. (Molecular Genetics and Genomics, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Exploring the impact of perceived biodiversity on psychological restoration along urban forest trails: A structural equation modeling approach - Ting Lei; Haitao Tang; Jiani Li; Guo Chen; Chunli Zhuo; Suping Gao; Qian Li; Xinyun Li (Urban Forestry & Urban Greening, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Acute liver injury and facial edema following ingestion of mushroom Descolea quercina - Ting Li; Xiu-Juan Li; Tai-Jie Yu; Wen-Hao Zhang; Yuan-Tian Lu; Yu-Xian Gao; Yuan-Yuan Xiong; Jun Gao; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Strong internal electric field-modulated carbon nitride for tetracycline photodegradation: Guidance by theoretical calculation and machine learning - Ting Wang; Wenhao Tang; Yang Lu; Chunbo Liu; Tianyu Zhou; Bo Feng (Environmental Research, 2026)

Riverine transport dynamics and historical trends of emerging and legacy flame retardants in an urbanized coastal zone: Pollutant management effectiveness in China - Jun-Rong Liang; Hui-Ping Wen; Ting Pan; Rui Tang; Lei Mai; Chen-Chou Wu; Ze-Hua Liu; Eddy Y. Zeng (Environmental Pollution, 2026)

FeSO4 combined with intermittent aeration promotes humification during rapeseed straw composting by sustaining Fe-ROS activity - Yang Xu; Ting-Ting Wang; Zhao-Yong Sun; Yuxin Xiao; Min Gou; Yue-Qin Tang (Chemical Engineering Journal, 2026)

Ubiquitination proteomics-based analysis to identify the key regulators of intramuscular fat deposition in Large White pigs and Erhualian pigs - Yuelei Zhao; Weilong Tang; Ting Li; Hao Jiang; Yuheng Li; Wei Wei; Jie Chen; Lifan Zhang (Food Chemistry, 2026)

Co-exposure to polyethylene microplastics and tetracycline alters nutritional quality, antioxidant capacity, amino acid profiles, and cultivation-associated microbiota of soybean sprouts - Lisha Deng; Wenjiang Zhou; Xiuzheng Zheng; Xuepeng Jin; Hongmei Jiang; Lanchai Chen; Jie Tang; Wenliang Xiang; Ting Cai (Food Bioscience, 2026)

Antioxidant peptides from fermented Nannochloropsis sp. alleviate ultraviolet B -induced oxidative stress in HaCaT keratinocytes and Drosophila melanogaster - Ting Yang; Gao Xi; Jindong Liu; Liuying Li; Lei Sun; Huanwen Tang; Huawen Li; Enqin Xia (Food Bioscience, 2026)

DART-HRMS combined with machine learning for rapid detection of camellia oil adulteration - Ting Liu; Binfeng Zhang; Zhanwei Yang; Lecheng Shen; Yuancong Zhang; Wenchao Tang; Mei Wang; Jing Li (Food Control, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Combined application of 1-methylcyclopropene and silicon-window modified atmosphere packaging delays cell wall degradation and softening in cold-stored ‘Saiwaihong’ apples - Cheng Zhao; Jiefen Cui; Hao Wu; Xuanming Tang; Xueping Wang; Mengyu Ma; Ting Liu; Yanfang Pan; Jinkai Zheng (Food Chemistry, 2026)

Short- and medium-term exposure to ambient air pollutants and severity of obstructive sleep apnea: A population-based study in Nanjing - Xia Tang; Haili Ren; Yuting Huang; Ting Xu; Daling Hu; Yizhang Xia; Tongda Xu; Quan Wang; Jiemiao Shen; Minghui Ji (Environmental Research, 2026)

Flexible and biodegradable pH fiber sensors for continuous monitoring of intestinal microenvironment in ulcerative colitis - Sijia Yu; Yixuan Liao; Qin Tang; Lu Yan; Yichao Yang; Yalan Deng; Dandan Zhu; Hao Zheng; Shuang Zhao; Ting Liu (Chemical Engineering Journal, 2026)

Tailored Cu active sites in 2D MOF-derived carbon nanosheets for dual electrochemical detection of chloramphenicol and paracetamol - Zhi-Lun Wu; Tsai-Ting Liu; Mei-Hong Tang; Sheng-Fei Lin; Yu-Jen Shih (Chemical Engineering Journal, 2026)

Role of TRPA1 channel activation in exacerbating allergic airway inflammation mediated by 4-Nitrodiphenylamine - Xiuying Chang; ChaoYue Sun; Quanling Zhang; Ting Xin; KeWei Wang; Xiaowen Tang; Zhen Qiao; Ningning Wei (Chemico-Biological Interactions, 2026)

Celastrol attenuates synovial inflammation and experimental arthritis by modulating PTGS2-associated ferroptosis resistance in fibroblast-like synoviocytes - Yunke Guo; Hao Tang; Zulayat Ablikim; Lirong Deng; Ting Wang; Mengjiang Tian (Journal of Molecular Histology, 2026)

Effects of photoperiod on gonadal development and neuropeptide Y and NPY1 receptor in Nile tilapia (Oreochromis niloticus) - Yujie Cao; Jun Xiao; Pengfei Gao; Yufang Chen; Zhanyang Tang; Liping Li; Zhongbao Guo; Ming Li; Zhuanling Lu; Ting Huang (Fish Physiology and Biochemistry, 2026)

The mechanism of intestinal-origin probiotics Lactococcus lactis M48 against sea perch iridovirus (SPIV) infection during sea perch Lateolabrax japonicus culture - Zheng Zhu; Yu-Min Xu; Pei-Qi Tang; Wu-Lang Luo; Wen-Feng Yang; Si-Ting Wu; Meng-Ke Liu; Xiao-Hong Huang; You-Hua Huang; Hong-Yan Sun; Qi-Wei Qin (Aquaculture, 2026)

Unraveling the complex interplay between glymphatic function, age, and brain structure in school-aged children with autism spectrum disorder - Zhongfeng Xie; Di Zhou; Shuchao Wang; Ting Hua; Hong Chen; Rong Yang; Yujiao Gong; Guangyu Tang; Lin Zhang; Xiaowen Xu (Brain Imaging and Behavior, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Differential effects of periphyton and rice straw decomposition on arsenic mobilization and methylation in flooded paddy soils - Bofan Chen; Wei Feng; Qingnan Huang; Zhao-Feng Yuan; Weiwei Zhai; Keli Zhao; Xianjin Tang; Ting Guo; Haibo Zhang (Journal of Environmental Management, 2026)

First detection of IncHI2 plasmid carrying blaNDM-5 in Escherichia coli from retail shellfish - Jun Yang; Chao Yue; Zixuan Wang; Huirong Tang; Ludan Xiao; Litao Lu; Haotian Deng; Lu-Chao Lv; Guangyu Liu; Yu-Ting Deng; Jian-Hua Liu (Food Research International, 2026)

Corrigendum to “Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry” [Food Chem. 511 (2026) 148850] - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Functional Characterization of CLE Peptides in Cotton Root Development Reveals GhCLE47 as a Key Regulator of Auxin-Mediated Root Architecture - Gai-Yuan Hu; Peng Liao; Xin-Yao Jiang; Ying-Chao Tang; Ting-Wan Li; Yang Li; Fu-Chun Xu; Zhen-Nan Zhang (Journal of Plant Growth Regulation, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Research trends and future perspectives on grazing management and grazing lands: A bibliometric analysis - Lu-ming Ding; Lei Liao; Bo Wang; Xue-mei Wang; Ting-yong Yang; Yi-guo Tang; Zalmen Henkin; Abraham Allan Degen; Wei-you Ou (Rangelands, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Long-term exposure to sandstorms-related particulate matter and risks of all-cause and cause-specific mortality in a national cohort study - Hailu Zhu; Xinran Shan; Xingyao Tang; Linhong Pang; Zhaoyang Pan; Zijun Li; Yicong Wang; Qi Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Journal of Hazardous Materials, 2026)

Lanthanum-modified biochar for dual removal of particulate/dissolved phosphorus in agricultural runoff: Performance and reuse as slow-release fertilizer - Ting Chen; Jiayi Lu; Fenghao Lin; Zhiqiang Chen; Junjie Wei; Jie He; Ying Wang; Xiujuan Tang; Jun Yin (Journal of Environmental Sciences, 2026)

Contact characteristics, damage evolution and aperture-seepage response of rough shale offset fractures subjected to vertical compressive stress - Wei Tang; Baoyi Chen; Cheng Zhai; Xingyu Wei; Ting Liu; Jizhao Xu; Yu Wang; Yangfeng Zheng (Geomechanics for Energy and the Environment, 2026)

Effect of molecular weight of chitosan on its complex coacervation with gelatin for oil encapsulation - Runyu Tang; Guangyi Kan; Ting Zhang; Huaiyue Sun; Xichang Wang; Jian Zhong (Food Chemistry, 2026)

Preparation, properties of bond energy-driven LKCC sequential drug-releasing hydrogel and its application in biofilm-infected wound repair - Jiangchuan He; Huan Wang; Yunhe Zheng; Yu Huang; Ting Wang; Hanchao Zhou; Kailai Liu; Yuchen Zhang; Jinpeng Wen; Jingya Qu; Pengchong Wang; Ling Liu; et al. (Chemical Engineering Journal, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

High frequency in vitro regeneration from embryonic tip of Wucai (Brassica campestris L.) - Danni Yang; Na Liao; Ting Li; Shiyong Zhang; Qian Yin; Xiaoyan Tang; Wenjie Wang; Lingyun Yuan; Chenggang Wang; Guohu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Quorum quenching as an emerging management tool for food contamination control - Nan Zhao; Xinyue Fan; Zhongyang Liu; Yiwei Jiang; Xinyi Chen; Yiting Tang; Ting Yu; Fujie Yan (Critical Reviews in Food Science and Nutrition, 2026)

Distribution and transport of trace organic contaminants from land to the coastal sea - Shi-Jie Lv; Ting Pan; Rui Tang; Jun-Rong Liang; Hui He; Lei Mai (Marine Pollution Bulletin, 2026)

Improving the prediction of optimal trim for container ships using enhanced feature engineering and machine learning techniques - Li Xuebin; Tang Zhengmao; Wang Ting; Zhang Wenjin (Ocean Engineering, 2026)

Carbothermal synthesis of quartz-supported S-nZVI from limonite and pyrite for enhanced organic pollutant degradation - Jiangan Chen; Ting Liao; Meian Wang; Mingxing Cheng; Danliang Zeng; Zuocheng Yuan; Wen Yu; Ying Ye; Wenjie Zhang; Qiongyao Tang; Chengdu Qi (Minerals Engineering, 2026)

Metabolomic and transcriptomic analyses reveal grafting-associated trade-offs between yield and flavonoids in Ziziphus jujuba var. spinosa - Mengyuan Zhang; Honghong Jiao; Xinbo Shi; Zhongxing Song; Jie Li; Guolong Li; Feng Jin; Ting Li; Zhishu Tang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

Unveiling the co-occurrence of fluoride-arsenic and nitrate retention in Wujiang cascade reservoirs by a hybrid hydrochemical, PMF model and multi-isotopic method - Tianna Zhang; Hongbo Wang; Leyan Feng; Hongyu Tang; Jiaju Liu; Ting Wang (Environmental Pollution, 2026)

Dietary copper induces cuproptosis and disrupts the gut-gonadal axis in zebrafish (Danio rerio) - Hongxing Chen; Can Tang; Kaile Huang; Wenji Zhou; Cheng Lou; Fangli Wu; Ting Huang; Yongju Luo; Lingtian Xie (Environmental Pollution, 2026)

Optimizing economy-energy-environment (3Es) policy mixes for decarbonization: Synergies, trade-offs, and regional implementation in China - Anping Ye; Yu-Jie Hu; Bao-Jun Tang; Ting Wang; Yao Tao (Energy Policy, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Performance Prediction Model for TBM Disc Cutters Considering Multi-Cutter Interactions and Joint Deterioration - Yizhe Peng; Hailong Zhang; Longfei Cheng; Ting Ren; Yang Tang; Jianjun Zhou; Zhuoran Zhou; Okubo Seisuke (Geotechnical and Geological Engineering, 2026)

When digital innovation misaligns: feedback processes across social, ecological, and technological domains in urban water governance - Yuxi Zhang; Yu-Ting Tang; Linjun Xie (Sustainability Science, 2026)

Regulation of EMT and cholangiocarcinoma metastasis by KIN17 through the mTOR signaling pathway - Yuxia Yang; Qianying Luo; Chuhong Huang; Xiaocong Lin; Lok Ting Chu; Qiuyan Li; Jinjing Tang; Tao Zeng (Molecular and Cellular Biochemistry, 2026)

Dopamine is a key regulator of the sexual receptivity switch in female Nasonia vitripennis - Jian-Qiu Cheng; Yi-Zhen Xu; Zi Wang; Peng-Cheng Liu; Ting Tang; Gen Zhang; Guan-Hong Wang; Hao-Yuan Hu (Animal Behaviour, 2026)

Magnetic biochar- loaded nano zero-valent iron for heavy metal passivation: Coupled interaction mechanism between arsenic and cadmium - Yi Hu; Huanhuan An; Xinquan Wei; Ting Liu; Xiao Tang; Li Hua; Dongmei Hou; Xiao Xiao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

Acclimation-enhanced ofloxacin biodegradation by Tetradesmus obliquus: Unveiling physiological and transcriptomic adaptation mechanisms - Wei Gao; Junzhuang Wu; Ting Guan; Imran Ali; Guoxin Tang; Yujiao Yue; Wei Li (Journal of Environmental Management, 2026)

A molecular dynamics Investigation of the evolution of coal pore structure and gas transport under High-Temperature steam treatment - Hao Qiu; Cheng Zhai; Yong Sun; Zhengzheng Tang; Jizhao Xu; Jing Huang; Ting Huang; Hongyang Xu; Yu Wang; Zongqing Tang (Fuel, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Highly effective core-shell CNF/HGM@CS/MXene electromagnetic interference composite films with superior flame retardancy - Yongqian Shi; Xiaoyong You; Haoxin Niu; Can Liao; Longcheng Tang; Jiefeng Gao; Pingan Song; Wei Zhang; Ting Qiu (Chemical Engineering Journal, 2026)

Efficiency and mechanisms of microbial metabolic regulator addition on carbon and nitrogen retention in biochar-assisted distilled grain waste composting - Shi-Peng Wang; Ting-Ting Wang; Xiu-Fang Li; Min Gou; Song-Tao Wang; Zhao-Yong Sun; Yue-Qin Tang (Bioresource Technology, 2026)

Protective role and mechanism of sonic hedgehog signaling pathway in spinal cord injury - Li Li Yin; Xiao Zhen Ji; Min Tang; Li Hui Chen; Jiu Zhou Lin; Ya Ling Jin; Wei Ting Chen (Molecular & Cellular Toxicology, 2026)

Dynamic evolution of dominant channels and fine particle migration paths in granitie residual soil under seepage coupling using in-situ dynamic contrast CT scanning - Yun Que; Jin Tang; Ting Qiu; Zhenliang Jiang; Shanghui Li; Bin Weng; Jianbin Liu (Journal of Soils and Sediments, 2026)

Distribution and Removal Efficiency of Microplastics in Urban Wastewater Treatment Plants - Ting Cai; Yunfeng Feng; Wenxiu Li; Tao Gu; Kaixiong Huang; Hui Luan; Chu Peng; Zhihe Tang (Bulletin of Environmental Contamination and Toxicology, 2026)

Transferrin confers imidacloprid resistance by attenuating ROS-induced apoptotic signaling in the white-backed planthopper, Sogatella furcifera - Kui Kang; Jun Gong; Ting Zhou; Xuexiao Du; Sijing Wan; Bin Tang; Lei Yue (Pesticide Biochemistry and Physiology, 2026)

Synthetic soil aggregate analogues: multi-functional montmorillonite-organic-microbial composites for mitigating soil acidification - Jian XIE; Ting GUI; Weijun LI; Lei LU; Geng SUN; Haiming TANG; Huihui DU (Pedosphere, 2026)

Effective removal of pollutants from sea cucumber aquaculture tailwater by two-stage adsorption and its mechanism - Ting Jia; Jin Hui; Wei Tang; Jie Yao; Na Tan; Wenjie Jin (Journal of Water Process Engineering, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Comprehensive characterization of real-fluid effects on autoignition behavior via high-order Virial equation of state coupled with ab initio multi-body intermolecular potentials - Mingrui Wang; Ruoyue Tang; Xinrui Ren; Hongqing Wu; Yuxin Dong; Ting Zhang; Bin Yang; Song Cheng (Fuel, 2026)

Preparation of responsive photonic crystals and their application in the detection of food hazards - Ting Li; Haihu Tan; Yang Liu; Chao Ge; Zhouyu Sun; Zengmin Tang; Ling Yang (Food Control, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Interlayer-engineered ammonium vanadate cathodes via Na+/PEG Co-intercalation for fast and stable Zn-ion storage - Jian Guo; Shuo Meng; Xiao Yan; Qiuxian Wang; Ting He; Lu Chen; Lujie Zuo; Ya Tang; Hongbin Zhao (Chemical Engineering Journal, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Performance and Mechanism of Sulfathiazole Adsorption by Magnetic Biochar: Promoting Effect of Co-existing Polystyrene and Simultaneous Removal - Xilong Zhang; Zihan Tang; Fei Liu; Xiuping Hong; Yingying Zhang; Ting Fang; Rongjian Fan; Xin Wang (Water, Air, & Soil Pollution, 2026)

EDTA-chelated and inorganic Cr(III) in rice: speciation-dependent bio availability controls root uptake dynamics - Jingjing Li; Kai Xu; Weichao Guo; Ting Liu; Shengsheng Sun; Tenghaobo Deng; Chao Jin; Yetao Tang; Rongliang Qiu (Plant and Soil, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Biodegradable microplastics as mediators of iron‑carbon decoupling: Enhanced soil carbon mineralization in wetland - Xinyi Huang; Yuan Pan; Xiansheng Zhang; Teng Li; Ting Wu; Shanqing Tang; Yunze Wang; Junhao Chen; Juanjuan Huang; Zhifeng Liu (Applied Soil Ecology, 2026)

Symbiotic interaction of Chlorella sp. and Shinella sp. for enhanced dissolved organic matter removal from sterilized mixed wastewater - Rumeng Lu; Qiaoyun Huang; Yunpu Wang; Xian Cui; Zhigang Yu; Naif Abdullah Al-Dhabi; Xiang Wang; Roger Ruan; Wangwang Tang; Zihan Li; Ting Zhou; Yuhuan Liu; et al. (Algal Research, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Synergistic quorum sensing by C4-HSL and C8-HSL boosts biofilm formation and pyridine degradation - Yuan Li; Min Gao; Changjie Zhu; Yingshun Lv; Ting Lei; Yao Peng; Xuan Liu; Mengyue Wang; Shuanshuan Tang; Yaxin Guo; Pengfei Wang (Journal of Environmental Chemical Engineering, 2026)

Progressive uncertainty-guided network for binary segmentation in high-resolution remote sensing imagery - Jiepan Li; Wei He; Ting Hu; Minghao Tang; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

KOH-modified biochar assisted distilled grain waste composting reduces carbon loss and accelerates humification via in-situ CO2 capture and microbial assimilation - Yang Xu; Shi-Peng Wang; Zi-Yuan Xia; Ting-Ting Wang; Song-Tao Wang; Min Gou; Ya-Ting Chen; Zhao-Yong Sun; Yue-Qin Tang (Chemical Engineering Journal, 2026)

Synergistic enhancement of CO2 capture via a dual-activator strategy: Mechanism insights into tertiary amine-boosted absorption and alcohol-facilitated regeneration - Xiaobin Zhou; Ting Zou; Yunqiong Tang; Shengpeng Mo; Yinming Fan; Bihong Lv; Yanan Zhang; Dunqiu Wang; Yinian Zhu; Zongqiang Zhu; Guohua Jing (Chemical Engineering Journal, 2026)

Optimizing soil microbial functions under long-term straw return enhances nutrient acquisition, thereby improving nutrient availability and crop productivity in tobacco–rice rotation systems of southern China - Bianhong Zhang; Rikun Li; Zhicheng Chen; Chunli Zeng; Songquan Liao; Yazhou Liu; Ting Cheng; Yifei Liu; Lina Tang; Wenxiong Lin; Jinwen Huang (Agriculture, Ecosystems & Environment, 2026)

Photolysis of hexa(methoxymethyl)melamine in aquatic systems: Critical roles of UV-shielding effect, hydrated electron and 3DOM* induced by dissolved organic matter - Jinfan Chen; He Liu; Dehao Song; Mei Wang; Ting Tang; Songhan Zeng; Sile Wu; Xiaodong Du; Xueqin Tao; Zhi Dang; Guining Lu (Water Research, 2026)

Toxicity evaluation of fosthiazate to Bombyx mori Linnaeus (Lepidoptera: Bombycidae): A new perspective from the chirality - Yuepeng Qiu; Jiyan Hu; Yao Feng; Yan Ma; Chang Li; Yazhu Liu; Yonghong Lai; Changcai Wu; Ruilong Sun; Ting Tang; Lianshan Li; Fengsong Liu (Pesticide Biochemistry and Physiology, 2026)

Water loss and return flows matter for water stress mitigation in China - Dan Wang; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Wei Zhang; Weili Ye; Guangxue Wu; Zhuo Chen; Huimei Li; Junxia Wang; Haoyuan Feng; Yuli Shan; et al. (Journal of Cleaner Production, 2026)

Hydrochemical characteristics, evolution, and controlling factors of a karstic river with reservoirs: Insights from spatial-temporal analysis - Jiang Wu; Ting Wang; Tang Liu; Jia-Ju Liu; Nan Xu; Hui Zeng; Ling-Yan He (Journal of Environmental Sciences, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Hierarchical porous aerogel constructed from in-situ assembled zein nanoparticles for sustainable radioactive iodine capture - Qing Shen; Cong Tang; Xiaoping Bai; Yujie Wen; Shijun Shao; Ting Huo; Shuqing Dong (Environmental Research, 2026)

The soil plastisphere: A hotspot for arsenic methylation regulated by microplastic polymer types - Kaimei Zhang; Wei Feng; Qingnan Huang; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Xianjin Tang; Haibo Zhang; Ting Guo (Environmental Research, 2026)

Sb(Ⅲ) oxidation by UV-based advance oxidation processes: Kinetics, radical contributions, influencing factors, and energy demand - Jinrong Lv; Min Liu; Lirong Zhu; Rui Tang; Zhongyue Liang; Ting Xie; Xuecai Tan; Bernard A. Goodman; Mengkai Li; Shaogang Liu (Chemical Engineering Journal, 2026)

Benzofuran-based covalent organic framework with regular fiber-rod structure for efficient photocatalytic H2O2 production under broad visible light - Ting Xu; Zhongxing Zhang; Zijing Wang; Yihao Zhang; Yayang Wang; Yaowen Wang; Liguang Lin; Ping Xue; Jiming Huang; Mi Tang; Lingjun Kong; Xiangcheng Li; et al. (Chemical Engineering Journal, 2026)

Glaucocalyxin A Promotes Spinal Cord Repair By Nrf2/HO-1 Pathway Activation to Suppress AIM2 Inflammasome Formation - Ze Li; Jiajing Ye; Zhiyu Fang; Xinyu Wu; Fang Tang; Ting Jiang; Yuhang Gong; Yuxuan Bao; Binbin Zheng; Huaxing Hong; Zhenghua Hong (Molecular Neurobiology, 2026)

Therapeutic Effects of Low-Intensity Treadmill Exercise on Motor and Non-Motor Symptoms in a 6-Hydroxydopamine (OHDA) Rat Model of Parkinson’s Disease via Gut–Brain Axis Modulation - Yu-Tang Tung; Tu-Hsueh Yeh; Shu-Ping Tsao; Chun-Hsu Pan; Wen-Chao Chen; Wei-Ting Shih; Chih-Hsuan Lou; Hui-Yu Huang (Molecular Neurobiology, 2026)

Photobiomodulation Reduces Fibrous Scar Formation After Spinal Cord Injury by Downregulating CXCL3 Expression in Macrophages - Zhihao Zhang; Hongwen Gu; Ting He; Yuanhang Zhao; Shilei Tang; Kangen Han; Yin Hu; Hongwei Wang; Hailong Yu (Molecular Neurobiology, 2026)

Linking Mitochondrial Gene Dysregulation to Immune Cell Shifts in Retinitis Pigmentosa - Jia Liang; Bo Wu; Xiangqing Hei; Lu Chen; Yuke Ji; Xiangcheng Tang; Lujia Feng; Fuying Guo; Huiyan Zheng; Yingying Diao; Ting Xie; Zhenhua Zou; et al. (Molecular Neurobiology, 2026)

Seasonal variation of the fastest-growing initial errors over the tropical Indian Ocean - Xunshu Song; Xiaojing Li; Youmin Tang; Ting Liu; Ruibin Ding (Climate Dynamics, 2026)

Humidity change in the upper-middle Yangtze River watershed during the MIS3 and its relationship to the East Asian Summer Monsoon - Liuliu Feng; Yixuan Wang; Runsheng He; Liang Tang; Ran Wei; Ting Chen (Quaternary Science Reviews, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Synergistic control of antibiotic resistance via natural illite-activated peroxymonosulfate: Efficiency and mechanism - Xiangqin Zhou; Ting Zhou; Jiuqiang Xiong; Wenjun Wang; Yingbin Li; Long Li; Xiang Tang; Zhuotong Zeng; Biao Song; Chengyun Zhou; Jing Tong (Journal of Hazardous Materials, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Utilizing food waste hydrolysate for enhanced microalgae protein production: a step towards circular economy - Sana Irshad; Ting Tang; Asad Nawaz; Yibing Zu; Zhihui Yuan; Yanming Li; Xu Liao; Zunhua Li; Meifeng Wang; Liangping Ni; Zuodong Qin (Journal of Cleaner Production, 2025)

Highly efficient antibiotic decontamination and biotoxicity elimination with activity-stability considerations via encapsulated catalyst induced peroxymonosulfate activation - Ting Yu; Naif Abdullah Al-Dhabi; Wenle Xing; Yangzhuang Zhu; Shikai Wang; Kanxin Jiang; Wangwang Tang (Journal of Environmental Management, 2025)

Lithium mineralization processes associated magmatic-hydrothermal evolution in the Xiaohusite No.91 pegmatite, Altai, NW China: Insights from in situ chemical and boron isotope variations in tourmaline - Jian-Zheng Chen; Yong Tang; Hui Zhang; Zheng-Hang Lv; Jing-Yu Zhao; Wen-Ting Huang; Jing-Tao Wang (Journal of Asian Earth Sciences, 2025)

Multi-omics network analysis of flavour formation in golden-flowered Tibetan dark tea processed by “flowering” using raw materials with different fermentation degrees - Ting Zhang; Zhiying Xu; Xue Yang; Meiyi Ning; Mengyi Ren; Xiao Liu; Yun Wang; Chunhua Li; Chen Xia; Manyou Yu; Shengxiang Chen; Xiaobo Tang; et al. (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Novel thermal modification of phosphate tailings for enhanced heavy metals immobilization in soil - Shengning Deng; Yanwei Hou; Zhao Liu; Youchi Zhang; Frederic Coulon; Yu-Ting Tang; Chao Cai (Environmental Research, 2025)

Rapid culture-free species identification and phenotypic antibiotic susceptibility test for polymicrobial infection by single-cell Raman spectroscopy - Miao Yu; Liliang Wang; Yiwen Xu; Jiyong Yang; Changsong Zhang; Ting Wang; Siyu Meng; Jingkai Wang; Qiang Zhao; Zhiqiang Zhang; Huijie Hu; Huan Zeng; et al. (Chemical Engineering Journal, 2025)

Hydrogen bonding enforced supramolecular multifunctional nanocoating for implant osseointegration - Junhong Qiu; Qianqian Qiu; Jiawei Yang; Weilong Tang; Jiarong Xu; Yujie Chen; Hao Cai; Yuqi Wan; Zhilin Yu; Conrado Aparicio; Zhihua Li; Zhou Ye; et al. (Chemical Engineering Journal, 2025)

Flexible and injectable hydrogen peroxide fiber sensor for early warning, real-time monitoring, and combination intervention in sepsis - Sijia Yu; Ying Jiang; Yiyang Liu; Qin Tang; Yixuan Liao; Yichao Yang; Shifang Peng; Yongheng Chen; Zheyuan Zhou; Ting Liu (Chemical Engineering Journal, 2025)

Isolation and characterization of a novel reassortant strain of Orthoreovirus mammalis from diarrheic pig - Jing-Ying Liao; Jia-Yao Hou; Yin Shi; Hui Tang; Yi-Shuai Zhang; Chao-Ting Xiao (Virus Genes, 2025)

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

Corrigendum to “the different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies” [toxicology and applied pharmacology volume 503, October 2025, 117505] - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Subfunctionalization, neofunctionalization, and nonfunctionalization of the four soybean phytochrome A genes - Lixin Ma; Ting Zhang; Sujun Ye; Wenmin Lin; Yinhua Lv; Wenmin Liu; Fanjiang Kong; Baohui Liu; Yang Tang; Xiaoya Lin (Plant Science, 2025)

Scour prediction, monitoring, and protection measures for offshore wind turbines: Recent advancements and insights - Jingcheng Cui; Ting Bao; Xuanming Ding; Chong Tang; Tianbo Li; Weizhen Zhou (Ocean Engineering, 2025)

Anti-acrolein from natural products by regulating miRNAs and targets - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Yi-Hong Tsai; Fang-Rong Chang; Tsu-Ming Chien; Hsueh-Wei Chang (Journal of Hazardous Materials, 2025)

Impact of wooden breast myopathy on meat quality and myofibrillar protein functionality in chicken - Xiaojie Yu; Fei Chen; Ting Tang; Chengfeng Sun; Rongxin Wen; Qianqian Yu (Food Chemistry, 2025)

Distinct effects of methylglyoxal-derived hydroimidazolone 1, N-carboxyethyllysine, and an advanced glycation end product-rich diet on lipid metabolism, gut microbiota, and secondary bile acids in high-fat diet-induced obese mice - Shih-Fang Huang; Yu-Ting Chang; Shih-Min Hsia; Kai-Wei Liao; Cheng-Yi Tsai; Shih-Yi Huang; Chi-Tang Ho; Wei-Lun Hung (Food Chemistry, 2025)

Lipidomics-based insights into the mechanism of muscle-specific quality differences during wet-aging - Ting Tang; Chengfeng Sun; Rongxin Wen; Zhenjun Zhao; Qianqian Yu (Food Chemistry, 2025)

Metal exposure and internalizing and externalizing psychobehavioral problems in a Chinese early adolescent cohort - Ting Tang; Min Li; Mengyuan Yuan; Yonghan Li; Cong Wang; Qi Zhong; Xueying Zhang; Yichao Huang; Fangbiao Tao; Puyu Su; Gengfu Wang (Environmental Research, 2025)

DSM design of perforated cold-formed steel lipped channel columns against local, local-distortional and distortional buckling: An experiment-based evaluation - Jing-Xuan Zhang; Liping Duan; Chunjiang Wang; Zhiyuan Tang; Ning Liu; Hai-Ting Li (Engineering Structures, 2025)

AI-Driven scenario discovery: Diffusion models and multi-armed bandits for building control validation - Wei-Ting Tang; Abraham P. Vinod; François Germain; Joel A. Paulson; Christopher R. Laughman; Ankush Chakrabarty (Energy and Buildings, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Naringenin targets and inhibits Monoamine Oxidase A/B to bidirectionally regulate intestinal motility. - Qi Li; Yi Chen; Yige Zhang; Canwei Xu; Ting Tang; Yunzhi Qian; Ong Shun seng; Yujuan Wang; Ling Fang; Tianshu Xu (Chemico-Biological Interactions, 2025)

Optimized co-combustion of paper-making solid wastes via, genetic algorithm: synergistic enhancement and coal-substitution potential - Ting Chen; Yuanfang Zhao; Jinhan Chen; Guohua Zhu; Jun Yin; Zhongcai Jin; Yiying Jin; Zhixin Yu; Zhigang Zhu; Xiujuan Tang (Waste Management, 2025)

The different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Coffin timber from southeastern China as a tree-ring archive for paleoclimate research - Zepeng Mei; Xin Jia; Duo Zheng; Feifei Zhou; Yu Xiao; Linping Ren; Wanru Tang; Di Zhang; Zhongcai Xiao; Min Zhou; Ting Guo; Xinyuan Kong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Mechanism of Cr(VI)-coexistence promoting malathion degradation by Shewanella oneidensis MR-1: Synergistic effects of enhanced membrane permeability and metabolic pathway remodeling - Jie Zhang; Ting Hu; Shen Tang; Yanhong Li; Huanlong Liu (Journal of Environmental Chemical Engineering, 2025)

Deciphering biphasic metabolic adaptation in Shewanella oneidensis MR-1: Riboflavin-driven antioxidant defense and propionate oxidation synergistic bioremediation of Cr(VI)-malathion co-contamination - Jingjing Peng; Ting Hu; Shen Tang; Yanhong Li; Peizhu Shi; Yu Cen; Jie Zhang (Journal of Environmental Chemical Engineering, 2025)

Different Effect of H2 and H-donating Solvent on Aromatic Formation during the Direct Coal Liquefaction of Naomaohu Coal - Ning Zhen; Xiao-Dong Zhou; Xue-Long Yin; Jing-Mei Liu; Ya-Kun Tang; Ting Liu; Lang Liu (Fuel, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Mechanisms underlying the chronic toxicity of ofloxacin to Daphnia magna: Oxidative stress, mitochondrial dysfunction, and energy allocation - Yuming Zhang; Xinling Tian; Haotian Li; Yajie Zhang; Yiwen Zhang; Manxin Chen; Zhihua Ni; Jihai Gu; Ting Tang; Song Xie; Fengsong Liu (Environmental Pollution, 2025)

Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Chlamydia trachomatis disrupts host metabolism in primary cervical epithelial cells - Heng Choon Cheong; Muhammad Ihsan Rommel; Yi Ying Cheok; Yee Teng Chan; Ting Fang Tang; Sofiah Sulaiman; Chung Yeng Looi; Bernard Arulanandam; Li-Yen Chang; Won Fen Wong (World Journal of Microbiology and Biotechnology, 2025)

Apigenin inhibits endothelial-to-mesenchymal transition of coronary artery endothelial cells and myocardial fibrosis by regulating ribosome biogenesis through GTPBP4 modulation - Xiaoyong Hu; Zhaoying Yang; Rui Tang; Zhongying Lv; Ting Zou; Yuanyuan Dou; Hongjian Li (Human Cell, 2025)

Multi-type vehicles’ contributions to air pollution using mobile monitoring and explainable machine-learning - Shikun Liu; Yi Tang; Yonghong Liu; Ting Gan; Xinru Yang (Transportation Research Part D: Transport and Environment, 2025)

Relieving the inhibition of propionate production by D-lactic acid via mixed culture fermentation - Jun Yin; Mingyang Chen; Jianyu Jin; Zhiqiang Chen; Xiujuan Tang; Ting Chen (Journal of Water Process Engineering, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

An alternate pathway of antimonite [Sb(III)] resistance in Ensifer adhaerens mediated by ArsZ’ - Ya-nan Wang; Shi-tong Tang; Ya-nan Sun; Xue-ting Li; Jun Zhang (Journal of Hazardous Materials, 2025)

Differential response of C3 and C4 plants in temperate grasslands to different grazing intensities and nitrogen addition - Ting Yuan; Jiatao Zhang; Shaohong Zhang; Shiming Tang; Yanlong Li; Weibo Ren; Wentao Mi; Jialu Liang (Journal of Environmental Management, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Biaxially oriented polyethylene (BOPE) and exogenous H2S extend strawberry shelf-life by increasing antioxidant activity and inhibiting pigment accumulation - Ying-Chun Song; Yu-Qi Zhao; Chi-Ming Tang; Pedro Garcia-Caparros; Si-Yu Yang; Jia-Qi Yu; Xiu-Ting Hu; Kang-Di Hu; Zhuo Han; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Hepatotoxicity of imidacloprid in zebrafish and the alleviating role of 10-hydroxy-2-decenoi acid: Insights into oxidative stress, inflammation, and gut microbiota - Yujing Tang; Yandong Zhan; Shuangshuang Gao; Ting Li; Hongzhuan Xuan (Journal of Hazardous Materials, 2025)

High value-added conversion of atmospheric pollutants and greenhouse gases: assessment of bottlenecks and optimization strategies for mainstream catalytic technology - Tao Zhong; Xianhu Long; Zhangnan Yao; Ting Li; Huinan Zhao; Su Tang; Shuanghong Tian; Chun He (Journal of Cleaner Production, 2025)

Identification of hemocyte types and characterization of their immune function in the house fly based on morphological observation and single-cell RNA sequencing - Jianming Zhang; Ting Tang; Dongdong Lin; Liya Ma; Fengsong Liu (Insect Biochemistry and Molecular Biology, 2025)

Two magmatic-hydrothermal events in Xinzhai Sn polymetallic deposit, Yunnan Province, China: Constraints from cassiterite U-Pb geochronology and elemental compositions of single fluid inclusions - Ying-Hua Chen; Wen-Chang Li; Ting-Guang Lan; Xiao-Yu Zhao; Ming-Guo Deng; Die Wang; Yan-Wen Tang; Ji-Huang Lai (Gondwana Research, 2025)

Efficiently hydrogenolysis of aromatic ether C-O bonds in lignite and model compounds over carbon-coated NiCo bimetallic catalyst - Caitao Chen; Juan Ma; Yakun Tang; Xiaohui Li; Guangbo Liu; Hanyao Song; Yingluo He; Noritatsu Tsubaki; Lang Liu; Ting Liu (Fuel, 2025)

Tailored super-microporous pitch-based carbon with small graphitic domains achieving high capacitive desalination performance - Xiang Bai; Lang Liu; Yakun Tang; Xiaodong Zhou; Ting Liu; Jingmei Liu; Youyuan Xu; Fengyun Ma; Dianzeng Jia (Desalination, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Surface Movement Law Caused by Continuous Mining: A Case Study of Loess Plateau Coal Mines - Junlei Xue; Fuquan Tang; Qian Yang; Tao Yuan; Jiakun Gao; Chao Zhu; Yu Su; Ting Ma (Natural Resources Research, 2025)

Upregulating mTOR/S6 K Pathway by CASTOR1 Promotes Astrocyte Proliferation and Myelination in Gpam−/−-induced mouse model of cerebral palsy - Zhaofang Chen; Liru Liu; Xiaolin Guo; Yage Zhang; Mengru Zhong; Yi Xu; Tingting Peng; Tingting Peng; Yuan Zhang; Qingfen Hou; Danxia Fan; Ting Gao; et al. (Molecular Neurobiology, 2025)

Deciphering the complex roles of leucine-rich repeat receptor kinases (LRR-RKs) in plant signal transduction - Ting Tang; Ferdinand Ndikuryayo; Xue-Yan Gong; Elaheh Amirinezhadfard; Mehtab Muhammad Aslam; Mo-Xian Chen; Wen-Chao Yang (Plant Science, 2025)

Converting methanogenesis into chain elongation for caproic acid production from food waste: Roles of pH and hydraulic retention time - Jialing Tang; Zongkun Hu; Yunhui Pu; Jingyun Chen; Yao Xiong; Ruoran Liu; Ting Li; Shah Faisal; Abdelfatah Abomohra (Journal of Environmental Management, 2025)

Tracking nutritional and quality changes in frozen pork: A 12-month study using 7 categories of meat parameters and VIS/NIR spectroscopy - Xi Tang; Hui Xiao; Ting Luo; Jiacheng Wei; Ruiqiu He; Junhui Duan; Shijun Xiao; Nengshui Ding; Lusheng Huang; Zhiyan Zhang (Food Chemistry, 2025)

Involvement of nerve cord-expressed SVWC2 in pathogen recognition and defense in Macrobrachium nipponense - Muyi Li; Nan Qin; Bowen Yuan; Minghao Guo; Likun Yang; Ting Tang; Fengchao Li; Fengsong Liu (Fish & Shellfish Immunology, 2025)

Magnetic biochar-supported nanoscale zero-valent iron for remediation of arsenic and cadmium-contaminated soils: The role of free radicals - Huanhuan An; Ting Liu; Xiao Xiao; Mengting Liu; Yi Hu; Pangzhi Wei; Weipeng Yao; Xiao Tang; Yongkang Lai; Xubiao Luo; Shenglian Luo (Environmental Research, 2025)

Construction of evaporator based on the principle of three primary colors to achieve synchronous photothermal conversion water evaporation and photocatalytic degradation - Zixiang Zhu; Ting Wang; Sijie Ren; Yachen Feng; Yihao Zhang; Shangshu Qian; Wanqi Tang; Xuepeng Yin; Tianpin Wu; Shanmin Gao (Desalination, 2025)

Experimental and computational investigation of mixing dynamics in millifluidic jet mixing reactors - Godstand Aimiuwu; Faiz Khan; David Mualen; Wei-Ting Tang; Nicholas A. Brunelli; Joel A. Paulson; Jessica O. Winter; Barbara Wyslouzil (Chemical Engineering Journal, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Unlocking the future potential of SWATH-MS: Advancing non-target screening workflow for the qualitative and quantitative analysis of emerging contaminants - Di Xia; Guofang Pan; Yaxiong Liu; He Liu; Bo Zhao; Jiahui Wu; Ting Tang; Guining Lu; Rui Wang (Water Research, 2025)

Neoproterozoic metasedimentary rocks in the eastern Songnen Massif, NE China: Implications for the early evolution and tectonic affinity of microcontinental massifs in the eastern Central Asian Orogenic belt - Yi-Ting Xue; Jie Tang; Wen-Li Hao; Jin-Peng Luan; Xin-Yu Long; Shuang Liang; Ji-Shuang Ding; Wen-Liang Xu (Precambrian Research, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

A three-in-one strategy of molecularly imprinted polymers-based electrochemical SERS for sensitive detection of acetamiprid in vegetables - Xuemei Tang; Ting Wu; Caiying Wang; Wei Zeng; Chengzhen Ji; Jing Wei; Long Wu (Food Chemistry, 2025)

Nitrogen‑phosphorus responses and Vis/NIR prediction in fresh tea leaves - Qing Luo; Ting Tang; Yuxin Duan; Junlin Li; Caijin Ling; Ting Gao; Weibin Wu (Food Chemistry, 2025)

In-situ solvent-free preparation of MOF/polymer composite electrolytes with highly dispersed and defected MOF nanoparticles for lithium-metal batteries - Junyan Tang; Dehua Wang; Wen Qin; Siyu Fang; Ting Xu; Jiming Huang; Mi Tang; Zhengbang Wang (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Strategic carbon source supplementation enhances nitrite degradation by Pantoea sp. A5 in variable temperature conditions - Tzu-Yuan Sung; Anil Kumar Patel; Shang-Ru Lin; Chuan-Ting Huang; Ying-Tang Huang (Bioresource Technology, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Impacts of water conservation, wastewater treatment, and reuse on water quantity and quality stress mitigation in China - Dan Wang; Zhuo Chen; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Yuli Shan; Wei Zhang; Weili Ye; Guangxue Wu; Huimei Li; Klaus Hubacek (Journal of Industrial Ecology, 2025)
Wastewater treatment plays a crucial role in removing pollutants. Water conservation and reuse of wastewater help to reduce freshwater use and to alleviate water stress. However, the extent to which water conservation, wastewater treatment, and reuse can contribute to water stress mitigation is not clear. This study aims to investigate the impact of water conservation, wastewater treatment, and reuse on both water quantity and quality stress mitigation in China. The investigation is based on a dataset mapping water quantity and pollutant flows across 32 sectors in 31 provinces in 2017 and a dataset of 7411 wastewater treatment plants containing information on wastewater quantity and quality. The findings show that wastewater reuse can reduce provincial water quantity stress by less than 10% and alleviate water stress in 4 out of 25 water‐stressed provinces. In contrast, water conservation can contribute to water quantity stress reduction by 31% on average. When water conservation measures and reuse are jointly implemented, quantity stress levels can significantly be alleviated in 19 out of 25 water‐stressed provinces, with quantity stress reductions ranging from 25% to 74%. The contribution of wastewater treatment to water quality stress mitigation varies between 6% and 86%, with an average of 29%. Nevertheless, wastewater treatment cannot sufficiently safeguard most regions against water quality stress. This is evident as 25 out of 29 water quality‐stressed provinces continue to suffer from quality stress despite implementing wastewater treatment and water conservation practices. Additional measures such as non‐point‐source pollution control should be implemented alongside wastewater treatment to eliminate provincial quality stress.

Development of regional soil desiccation cracking susceptibility assessment model using GIS-based fuzzy comprehensive evaluation - Ting Wang; Chao-Sheng Tang; Zhi-Xiong Zeng; Ben-Gang Tian; Jin-Jian Xu; Qing Cheng; Zheng-Tao Shen; Xiao-Hua Pan (Bulletin of Engineering Geology and the Environment, 2025)

Deep learning approach for reconstructing three-dimensional distribution of NO2 on an urban scale - Zhiguo Zhang; Qihua Li; Qihou Hu; Jingkai Xue; Ting Liu; Zhijian Tang; Fan Wang; Chengxin Zhang; Chuan Lu; Zhiman Wang; Meng Gao; Cheng Liu (Remote Sensing of Environment, 2025)

Prevalence of Clostridium perfringens in sheep (Ovis aries) and goat (Capra hircus) populations across Asia: A systematic review and meta-analysis - Wen-Xu Tan; Tong Ye; Qi-Man Zhang; Miao Zhang; Xiao-Tong Chen; Lu-Yao Tang; Meng-Ting Yang; Jing Jiang; Quan Zhao (Research in Veterinary Science, 2025)

Foliar-applied zinc promotes cadmium allocation from leaf surfaces to grains in rice - Ya-Ting Liu; Bo-Fang Yan; Xuan Cai; Hong-Xiang Zheng; Rong-Liang Qiu; Ye-Tao Tang (Journal of Environmental Sciences, 2025)

Prediction of chlorination degradation rate of emerging contaminants based on machine learning models - Yufan Du; Ting Tang; Dehao Song; Rui Wang; He Liu; Xiaodong Du; Zhi Dang; Guining Lu (Environmental Pollution, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

SIRT3 regulates PFKFB3-mediated glycolysis to attenuate cisplatin-induced ototoxicity both in vivo and in vitro - Wei Tang; Shimin Zong; Peiyu Du; Xuan Yu; Ting Li; Bo Liu; Yu Zhong; Wenyang Lei; Wenting Yu; Hongjun Xiao (Archives of Toxicology, 2025)

Comammox Nitrospira are the dominant ammonia oxidizers in the Yangtze estuarine biofilms - Xiu-feng Tang; Xing-pan Guo; Lu Kuang; Xin-jie Chen; Nazupar Sidikjan; Ting-ting Xu; Shan Jiang; Min Liu; Li-jun Hou; Yi Yang (Water Research, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Navigating nanotoxicity: Unraveling nanomaterial-induced effects via multi-omics integration - Zhihui Wang; Ting Zhang; Meng Tang (NanoImpact, 2025)

Dual-identity microrobots - Ting Chen; Sirui Lu; Caiyan Lai; Yongcheng Li; Jie Yang; Jiamin Tang; Kai Huang; Yuepeng Cai; Renfeng Dong (Chemical Engineering Journal, 2025)

Efficient photoreforming of organic solvents into CH4 over 2D donor-π-acceptor conjugated polymers with tunable symmetry - Guoen Tang; Xiangjing Xie; Guanhui Liu; Ting Song; Xiayi Hu; Bei Long; Guo-Jun Deng; Mahmoud Sayed (Chemical Engineering Journal, 2025)

Transgenic soybean expressing Cry1Ab-Vip3A fusion protein confers broad-spectrum resistance to lepidopteran pest - Zhenzhi Pan; Yanxiang Zhu; Chaoyang Lin; Mengzhen Tang; Zhicheng Shen; Ting Zheng (Plant Cell Reports, 2025)

Sphingosinicella rhizophila sp. nov., Isolated from Oat (Avena sativa L.) Rhizosphere Soil - Yuze Guo; Kai Tang; Ting Yao; Jieyuzheng Zhang; Yang Liu; Jianyu Meng; Fuying Feng (Current Microbiology, 2025)

UVMSR: a novel approach to hyperspectral image super-resolution by fusing U-Net and Mamba - Ting Tang; Weihong Yan; Geli Bai; Xin Pan; Jiangping Liu (International Journal of Remote Sensing, 2025)

Toward Sustainable Fisheries: Lessons Learnt from Taiwan’s Offshore and Coastal Fishery Policy - Kuo-Huan Ting; Hao-Tang Jhan; Chih-Cheng Lin; Wen-Hong Liu (Coastal Management, 2025)

Interactions between nanoplastics and Tetrahymena thermophila: Low toxicity vs. potential biodegradation - Aiyun Li; Fengyu Yuan; Lianshan Li; Jihai Gu; Yuming Zhang; Fengchao Li; Ting Tang; Fengsong Liu (Chemosphere, 2025)

The mechanisms of tripterygium glycosides-induced reproductive toxicity and detoxification strategies - Zechen Niu; Huanhuan Zhang; Chunzhou Cai; Ting Yang; Tian Ma; Dingqiao Xu; Dongxiao Cui; Yuping Tang (Reproductive Toxicology, 2025)

Suppression of Adipokinetic hormones enhances Ascovirus HvAV-3h killing speed in Helicoverpa armigera - Zhengkun Xiao; Jiajun Gao; Jun Tang; Ting Xiao; Jianjun Hu; Yuhan Xie; Heba A.H. Zaghloul; Guo-Hua Huang (Pesticide Biochemistry and Physiology, 2025)

Aluminum promotes B1 cells to produce IL-10 and impairs adaptive immune system - Ting Liu; Wei Wang; Jun Du; Hongyue Liu; Jiaojiao Wu; Chuanxuan Wang; MengKe Tang; Yalin Liu; Yingzi Ju; Weidong Qu; Jianheng Zheng; Yifan Zhao; et al. (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Fabrication of robust and efficient boronic acid-functionalized porphyrin-based metal–organic framework for selective adsorption of adenosine - Juan Zhang; Ting Zou; Furong Tang (Chemical Engineering Journal, 2025)

Electron delocalization engineering via hierarchical modulation in single-atom catalysts for highly efficient electrochemical CO2 reduction - Xu Han; Hong Liu; Pengfei Cao; Weiqiang Tang; Chao Yue Zhang; Martí Biset-Peiró; Ke Xiao; Pengyi Tang; Marc Heggen; Miquel Vega-Paredes; Alba Garzón Manjón; Lirong Zheng; et al. (Chemical Engineering Journal, 2025)

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

The Systematic Analysis of the Impact of China Water Improvement and Fluoride Reduction Project on Children - Bo Yang; Feiqing Wang; Xu Yang; Jinyang Cheng; Juan Chen; Bingbing Li; Ying Zhou; Xiaoxu Chen; Bo Wei; Xiaoshuang Yuan; Ting Tian; Dongxin Tang; et al. (Biological Trace Element Research, 2025)

Organic-inorganic geochemistry and paleontology reveal the Paleocene paleoecology and source rock development in the Lishui-Jiaojiang Sag, East China Sea Shelf Basin - Jiahao He; Dujie Hou; Youjun Tang; Ting Wang; Jun Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

The first application of high-order Virial equation of state and ab initio multi-body potentials in modeling supercritical oxidation in jet-stirred reactors - Mingrui Wang; Ruoyue Tang; Xinrui Ren; Hongqing Wu; Ting Zhang; Song Cheng (Fuel, 2025)

Multi-Omics analysis reveals the sensory quality and fungal communities of Tibetan teas produced by wet- and dry-piling fermentation - Shengxiang Chen; Mengxue Zhang; Shijie Luo; Meiyi Ning; Yuxi Chen; Liqiang Tan; Xiaobo Tang; Xiao Liu; Liang Zheng; Aafke Saarloos; Ting Zhang; Chen Liu (Food Research International, 2025)

A combined drying process involving hot air and roasting for improving summer congou black tea quality - Fei Liu; Hongkai Zhu; Chunhua Li; Yun Wang; Juan Zhang; Xiaobo Tang; Ting Zhang; Yueyun Liu (Food Research International, 2025)

Development of a novel ternary MOF nanozyme-based smartphone-integrated colorimetric and microfluidic paper-based analytical device for trace glyphosate detection - Ting Zhang; Miao Tang; SiYi Yang; Huanbao Fa; Yongzhong Wang; Danqun Huo; Changjun Hou; Mei Yang (Food Chemistry, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

Solid-state ion-conductive elastomers with high mechanical robustness and ion-conductivity for highly durable triboelectric nanogenerators - Fangyan Ou; Xinze Li; Liang Tuo; Zhichao Zhang; Wei Tang; Ting Xie; Chuang Ning; Wenyu Pan; Qizhi Chen; Qihua Liang; Zhiyong Qin; Wei Gao; et al. (Chemical Engineering Journal, 2025)

Novel peptide inhibitor of matrix Metalloproteinases-1 from pufferfish skin collagen hydrolysates and its potential Photoprotective activity via the MAPK/AP-1 signaling pathway - Bei Chen; Shuilin Cai; Lulu Cui; Ting Yu; Kun Qiao; Yongchang Su; Min Xu; Haiyan Tang; Shuji Liu; Ming Yang; Zhiyu Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Enhanced poly(3-hydroxybutyrate-co-3-hydroxyvalerate) production from volatile fatty acids by Halomonas sp. YJ01 with 2-methylcitrate cycle - Jincan Yang; Jing Wang; Xiaoqin Yu; Ting Chen; Jun Yin; Xiujuan Tang (Journal of Environmental Management, 2025)

Turning coal hydrogenation liquefaction residue into high conductivity carbon black with magnesium citrate-assisted steam activation followed by high temperature treatment - Qian Meng; Huiping Sun; Yiyang Rong; Mengxue Tang; Yan Tan; Ting Liu; Zizhen Ma; Huawei Zhang (Fuel, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Changes of bacterial necromass and their roles in humus conversion during organic wastes composting from different sources - Wenjie Chen; Yan Yang; Su Chang; Yuquan Wei; Zhen Wu; Kaiyan Tang; Yuan Chang; Yifan Zhang; Ji Li; Ting Xu; Xia Liang (Bioresource Technology, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

Endophytic Bacteria Enterobacter cloacae PN7 Promotes Biosynthesis and Accumulation of Saponins in Panax notoginseng - Xianjing Lin; Mulan Wang; Feiyan Xie; Yuxi Cheng; Li Yang; Jian Gao; Weiqi Li; Xudong Zhang; Ting Tang (Current Microbiology, 2025)

Tracing contaminants of emerging concern and their transformations in the whole treatment process of a municipal wastewater treatment plant using nontarget screening and molecular networking strategies - Zhenguo Chen; Di Xia; Huangrui Liu; Rui Wang; Mingzhi Huang; Ting Tang; Guining Lu (Water Research, 2024)

Investigating the environmental dynamics of emerging pollutants in response to global climate change: Insights from bibliometrics-based visualization analysis - Bogui Pan; Hong Tian; Boyou Pan; Ting Zhong; Miao Xin; Jinhua Ding; Junyu Wei; Hong-Jia Huang; Jing-Qian Tang; Fengtao Zhang; Nai-Xian Feng; Ce-Hui Mo (Science of The Total Environment, 2024)

Interactive effects of microplastics and cadmium on soil properties, microbial communities and bok choy growth - Mengxiao Li; Jiaju He; Xiaofeng Chen; Xiaoman Dong; Shuang Liu; Christopher W.N. Anderson; Minghua Zhou; Xuesong Gao; Xiaoyan Tang; Di Zhao; Ting Lan (Science of The Total Environment, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Effect of inoculum sources on caproic acid production from food waste through lactate-based chain elongation: Properties and microbial succession - Jialing Tang; Hao Yang; Yunhui Pu; Zongkun Hu; Yao Xiong; Jingyun Chen; Ruoran Liu; Ting Li; Shah Faisal; Abdelfatah Abomohra (Journal of Environmental Chemical Engineering, 2024)

Development of arcuate faults and controls on hydrocarbon accumulation in the Tiantai slope, Xihu Depression, East China Sea basin - Lang Yu; Yixin Yu; Yiming Jiang; Wei Zou; Gongcheng Zhang; Xianjun Tang; Ting Tang; Xinxin Liang; Xinjian He; Dongxia Chen (Journal of Asian Earth Sciences, 2024)

Effect of inoculation with different Eurotium cristatum strains on the microbial communities and volatile organic compounds of Fu brick tea - Yu Xiao; Hui Chen; Yulian Chen; Chi-Tang Ho; Yuanliang Wang; Ting Cai; Shi Li; Jinrong Ma; Tianyang Guo; Liang Zhang; Zhonghua Liu (Food Research International, 2024)

Fe (hydr)oxides and organic colloids mediate colloid-bound chromium mobilization in Cr(VI) contaminated paddy soil - Ting Liu; Ran Wei; Jingjing Li; Weipeng Xie; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Environmental Pollution, 2024)

A comprehensive framework for characterizing and quantifying soil desiccation crack patterns: Quantitative parameters and development of CIAS - Chao-Sheng Tang; Ben-Gang Tian; Qing Cheng; Ting Leng; Bin Shi (Engineering Geology, 2024)

Linear π-conjugated organic cathodes with dispersed redox-active units for high performance aqueous zinc-ion batteries - Ting Xu; Lun Su; Caiyi Ku; Yihao Zhang; Lei Chen; Quan Gou; Siyu Fang; Ping Xue; Mi Tang; Chengliang Wang; Zhengbang Wang (Chemical Engineering Journal, 2024)

Highly selective capture of lead(II) by a barium-zinc-antimony-oxo cluster-based material: Ion-exchange pathway with single-crystal-to-single-crystal structural transformation - Wei-Yang Wen; Jia-Hua Luo; Hai-Yan Sun; Yu-Wei Ren; Lu Yang; Tian-Yu Pan; Jun-Hao Tang; Wen Ma; Jia-Ting Liu; Bing Hu; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Evaluations of storm tide hazard along the coast of China using synthetic dynamic tropical cyclone events - Jian Yang; Yu Chen; Yanan Tang; Zhongdong Duan; Guirong Yan; Jinping Ou; Ting Gong; Zhe Yang; Jianming Yin (Coastal Engineering, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

MBSFC: hyperspectral image classification based on multi-branch and spectral feature conversion - Ting Tang; Shaopeng Liu; Xueliang Fu; Weihong Yan; Xiaoling Luo; Xin Pan (International Journal of Remote Sensing, 2024)

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Designing ballastless high-speed railways in frozen regions: A dynamic analysis using three-dimensional numerical modelling - Shuang Tian; Liang Tang; Xianzhang Ling; Shi Liu; Ting Li (Transportation Geotechnics, 2024)

Uncovering the spatial characteristics of global net anthropogenic nitrogen input at high resolution and across 1.42 million lake basins - Jincheng Li; Yanxin Sun; Yue Qin; Ting Tang; Taher Kahil; Peter Burek; Gang Zhao; Kaikui Cai; Qingsong Jiang; Yong Liu (Science of The Total Environment, 2024)

Optimizing greywater treatment in green walls: A comparative analysis of recycled substrate materials - Olivia Addo-Bankas; Ting Wei; Cheng Tang; Yaqian Zhao (Journal of Water Process Engineering, 2024)

Performance and mechanism of diclofenac adsorption onto 3D poly(m-phenylenediamine)-grafted melamine foam via batch experiment and theoretical studies - Ting Xiong; Xintao Xu; Chao Tang; Hai Guo; Wenjun Wang; Milan Liu; Jiayin Guo; Hou Wang; Lijian Leng; Bing Liu; Xingzhong Yuan (Journal of Environmental Management, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Introducing electron-rich thiophene bridges in hot exciton emitter for efficient non-doped near-infrared OLEDs with low turn-on voltages - Ruming Jiang; Zhangshan Liu; Yuanyuan Han; Jiawei Long; Ting Guo; Xia Lan; Mingguang Yu; Ting Fan; Haijun Ma; Yen Wei; Ben Zhong Tang; Zujin Zhao (Chemical Engineering Journal, 2024)

Formation of Na-O bonds in NaZn(BH4)3·xTHF for enhancing sodium conductivity - Qijing Gao; Dingguan Liang; Ting He; Liang Tang; Minghong Wu; Wenqian Chen (Chemical Engineering Journal, 2024)

Hydrogen peroxide participates in leaf senescence by inhibiting CHLI1 activity - Shi-Jia Wang; Shuang Zhai; Xin-Tong Xu; Ying-Tang Lu; Ting-Ting Yuan (Plant Cell Reports, 2024)

TRIM28 Fosters Microglia Ferroptosis via Autophagy Modulation to Enhance Neuropathic Pain and Neuroinflammation - Jian Tang; Qi Chen; Li Xiang; Ting Tu; Ying Zhang; Cehua Ou (Molecular Neurobiology, 2024)

Large-Scale Triaxial Test on Mechanical Behavior of Coral Sand Gravel Layered Samples - Xinyue Tang; Dongfeng Xin; Xuewen Lei; Ting Yao; Qingshan Meng; Qingbing Liu (Journal of Marine Science and Engineering, 2024)
Layered structures comprising coral sand and gravel have been observed in hydraulic filled foundations in the coral reefs in the South China Sea, leading to anisotropy in their physical and mechanical properties. However, the effect of a layered structure on the strength and deformation of the coral soil foundation remains unclear. In this study, a series of large-scale triaxial compression tests and step-loading tests were carried out on four types of samples, i.e., clean coral sand, clean coral gravel, sand-over-gravel layered sample, and gravel-over-sand layered sample, to investigate the impact of confining pressure and the layered structure on the strength and failure modes of these soils. The results indicate that the stress–strain relationships of all samples predominantly exhibit strain hardening under drained conditions. Under identical confining pressures, the peak strength of clean coral sand is the lowest, while that of coral gravel is the highest. The peak strengths of the two layered samples fall between these extremes, with the gravel-over-sand layered sample exhibiting higher strength. All four samples have similar peak friction angles, slightly exceeding 40°. The difference in peak strength among the four types of samples is attributed to the variations in cohesion, with the cohesion of clean coral gravel being up to four times that of clean sand, and the cohesion of layered samples falling between these two. Both clean sand and clean gravel samples exhibit a bulging phenomenon in the middle, while the layered samples primarily exhibit bulging near the coral gravel layer. In the step-loading tests, the bearing capacity of the layered samples falls between those of clean coral sand and coral gravel, with the gravel-over-sand layered samples demonstrating higher strength. Moreover, the p-s curve of the gravel-over-sand layered samples obtained from the large-scale triaxial apparatus under a confining pressure of 400 kPa resembles that from the plate load tests on the same samples.

Decreased nitrogen deposition in Beijing over the recent decade and its implications - Ruotong Si; Ziyin Yu; Xin Ma; Zhang Wen; Ting Luo; Wen Xu; Lei Liu; Aohan Tang; Kai Wang; Lin Zhang; Andreas Schweiger; Keith Goulding; et al. (Science of The Total Environment, 2024)

Potential powered EC-SERS for sensitive detection of acetamiprid - Ting Wu; Xuemei Tang; Wei Zeng; Yu Han; Sihang Zhang; Jing Wei; Long Wu (Journal of Food Engineering, 2024)

Study on electrocatalysis NORR properties to produce NH3 over the Cu-based catalyst modified by Co-doping using in-situ electrodeposition method - Fengyu Gao; Ting Sun; Yaru Lei; Shunzheng Zhao; Yaxin Niu; Honghong Yi; Yuansong Zhou; Xiaolong Tang (Fuel, 2024)

Muscle LIM protein of Macrobrachium nipponense (MnMLP) involved in immune and stress response - Ting Tang; Mengjia Wu; Likun Yang; Fengsong Liu; Feng Zhang (Fish & Shellfish Immunology, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Promoting charge separation in conjugated polymer for superior photocatalytic decomposition of DMSO to CH4 under sunlight illumination - Guoen Tang; Yizheng Chen; Ting Song; Xiayi Hu; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2024)

Correction: Edaravone Maintains AQP4 Polarity Via OS/MMP9/β-DG Pathway in an Experimental Intracerebral Hemorrhage Mouse Model - Zhenhua Wang; Yuan Li; Zhixu Wang; Yuhui Liao; Qingqing Ye; Shilong Tang; Ting Wei; Pengyu Xiao; Juan Huang; Weitian Lu (Molecular Neurobiology, 2024)

Edaravone Maintains AQP4 Polarity Via OS/MMP9/β-DG Pathway in an Experimental Intracerebral Hemorrhage Mouse Model - Zhenhua Wang; Yuan Li; Zhixu Wang; Yuhui Liao; Qingqing Ye; Shilong Tang; Ting Wei; Pengyu Xiao; Juan Huang; Weitian Lu (Molecular Neurobiology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Intraspecific rDNA FISH-based karyological variation corresponding to the phenotypic diversity of Rosa praelucens Byhouwer - Hongying Jian; Qiao Fang; Shirui Cao; Ting Zhang; Min Tian; Kaixue Tang (Genetic Resources and Crop Evolution, 2024)

Can Turbidity Data from Remote Sensing Explain Modelled Spatial and Temporal Sediment Loading Patterns? An Application in the Lake Tana Basin - Albert Nkwasa; Rediet Esayas Getachew; Katoria Lekarkar; Estifanos Addisu Yimer; Analy Baltodano Martínez; Ting Tang; Ann van Griensven (Environmental Modeling & Assessment, 2024)
Understanding the spatial and temporal patterns of sediment loading in water bodies is crucial for effective water quality management. Remote sensing (RS) has emerged as a valuable and reliable tool for monitoring turbidity, which can provide insights into sediment dynamics in water bodies. In this study, we investigate the potential of turbidity data derived from RS to explain simulated spatial and temporal sediment loading patterns in the Lake Tana basin, Ethiopia. Utilizing existing RS lake turbidity data from Copernicus Global Land Service (CGLS) and simulated seasonal and multiyear trends of river sediment loadings into Lake Tana from the Soil and Water Assessment Tool (SWAT + model), we estimate correlations at different river inlets into Lake Tana. The results reveal a strong positive correlation ( R 2 > 0.66) between the multiyear monthly average sediment load from inflow rivers and RS lake turbidity at most river inlets. This indicates that the simulated river sediment loads and lake turbidity at river inlets exhibit similar seasonal patterns. Notably, higher turbidity levels are observed at the river inlet with the highest sediment load export. These findings highlight the potential of RS turbidity products in characterizing temporal and spatial patterns of sediment loadings, particularly in data-scarce regions, contributing to a better understanding of water quality dynamics in such areas.

Impact of nitrogen enrichment on the functions of extracellular enzymes in ectomycorrhizal community and nutrient status of pine seedlings - Panting Tang; Chen Ning; Ting Liu; Zhiming Tan; Xue Wang; Shuguang Liu; Wende Yan (Applied Soil Ecology, 2024)

Enhancement of light-driven adsorption efficacy through the integration of NiCo2O4 onto CeO2 for photo-ozone catalytic degradation of toluene - Ting Zhang; Lingling Tang; Baolin Chang; Junxian Gao; Ji Li; Jinze Lyu (Chemosphere, 2024)

The analysis of growth performance and expression of growth-related genes in natural gynogenic blunt snout bream muscle derived from the blunt snout bream (Megalobrama amblycephala, ♀) × Chinese perch (Siniperca chuatsi, ♂) - Ping Wu; Wangwang Ji; Ya Zeng; Jie Tang; Chang Wu; Qinbo Qin; Ting Yi; Yi Zhou; Rurong Zhao; Min Tao; Chun Zhang; Chenchen Tang; et al. (Aquaculture, 2024)

BpAFP, a Broussonetia papyrifera latex chitinase, exhibits a dual role in resisting to both Verticillium wilt disease and lepidopterous pests, Plutella xylostella and Prodenia litura - Xianbi Li; Dan Jin; Feifei Yi; Meng Tang; Siyi Wan; Yanhua Fan; Yuehua Xiao; Ting Liu; Hui Li; Jiancong Li; Mingliang Qiu; Yan Pei (Plant Science, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

Numerical study on regenerative cooling technology with endothermic hydrocarbon fuel: A comprehensive review - Ke Tian; Ping Yang; Zicheng Tang; Zhilong Cheng; Jin Wang; Min Zeng; Qiuwang Wang; Ting Ma (Journal of Cleaner Production, 2024)

Assessing sustainable development pathways for water, food, and energy security in a transboundary river basin - Amanda Palazzo; Taher Kahil; Barbara A. Willaarts; Peter Burek; Michiel van Dijk; Ting Tang; Piotr Magnuszewski; Petr Havlík; Simon Langan; Yoshihide Wada (Environmental Development, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Revealing the mechanism behind the highly selective separation of 1,4-butyrolactone from n-methylpyrrolidone using nonporous adaptive crystals of perethylated pillar[5]arene - Minlei Yin; Chen Yang; Duanlian Tang; Shiyin Huang; Xiaoyu Lou; Rongkai Cui; Changshen Ye; Jie Chen; Ting Qiu (Chemical Engineering Journal, 2024)

Organelle synergy unleashed: Modulating mitochondrial-endoplasmic reticulum contacts with a self-assembled prodrug amplifies ferroptosis for innovative cancer therapy - Junyan Zhuang; Renming Fan; Weike Liao; Ruizhuo Lin; Aohua Deng; Ting Zhao; Yongrui Hai; Heran Li; Lei Tang; Gaofei Wei (Chemical Engineering Journal, 2024)

A New Method for Groundwater Pollution Investigation - Yulan Tang; Xiaohan Zhang; Hongda Wang; Wenlong Li; Diannan Huang; Ting Li (Water, Air, & Soil Pollution, 2024)

Analysis of Fracture Network Formation Mechanisms and Main Controlling Factors of Methane Explosion Fracturing in Deep Shale Reservoir - Yu Wang; Cheng Zhai; Ting Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; Wei Tang; Yangfeng Zheng; Ning Luo (Rock Mechanics and Rock Engineering, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Combined use of chemical dust suppressant and herbaceous plants for tailings dust control - Yonghao Yang; Zhihao Luo; Zuoan Wei; Junkang Zhao; Ting Lu; Tianbao Fu; Shuang Tang (Environmental Geochemistry and Health, 2024)

Activation of GPR30 Ameliorates Cerebral Ischemia–Reperfusion Injury by Suppressing Ferroptosis Through Nrf2/GPX4 Signaling Pathway - Yong-qiang Zhang; Ting Sun; Zhen Zhao; Jing Fu; Le Yang; Yuan Xu; Jing-feng Zhao; Xiu-ling Tang; An Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2024)

Universal materials model of deep-learning density functional theory Hamiltonian - Yuxiang Wang; Yang Li; Zechen Tang; He Li; Zilong Yuan; Honggeng Tao; Nianlong Zou; Ting Bao; Xinghao Liang; Zezhou Chen; Shanghua Xu; Ce Bian; et al. (Science Bulletin, 2024)

Deciphering how promoting land consolidation for village revitalization in rural China: A comparison study - Yanfeng Jiang; Hualou Long; Yu-ting Tang; Wu Deng (Journal of Rural Studies, 2024)

Association of metals with early postnatal gut microbiota among infants admitted to the neonatal intensive care unit - Shi-ting Xiang; Changci Zhou; Kunyan Zhao; Ye Ma; Ruiwen Huang; Yunlong Peng; Yan Tang; Fei Yang; Jun Qiu (International Journal of Hygiene and Environmental Health, 2024)

Porous hollow nanospheres nickel phosphide and its high catalytic hydrogenation performance on naomaohu coal soluble portion and model compounds - Yingxiong Zhang; Ting Liu; Yakun Tang; Jingmei Liu; Yue Zhang; Xiaodong Zhou; Xiaohui Li; Lang Liu (Fuel, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

A novel long non-coding RNA linc-93.2 participates in bisphenol induced oxidative stress and macrophage polarization in red common carp (Cyprinus carpio) - Ting Yu; Qing Wei; Yiran Tang; Ling Cai; Bei Chen; Ming Yang (Fish & Shellfish Immunology, 2024)

Corrigendum to “Size distribution and lung-depostion of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays” [Environ. Pollut. 336 (2023) 122437] - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2024)

Marine anticancer drugs in modulating miRNAs and antioxidant signaling - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Kuo-Chuan Wu; Fang-Rong Chang; Yi-Hong Tsai; Tsu-Ming Chien; Hsueh-Wei Chang (Chemico-Biological Interactions, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Exploring the Roles of m6A-Modified circRNAs in Myasthenia Gravis Based on Multi-Omics Analysis - Shuang Li; Yu Zhang; Geyu Liu; Na Song; Zhe Ruan; Rongjing Guo; Yonglan Tang; Xiangqi Cao; Xiaoxi Huang; Ting Gao; Sijia Hao; Qingqing Wang; et al. (Molecular Neurobiology, 2024)

Capability of S. oneidensis MR-1 for malathion degradation: Insights from physiological and biochemical analyses - Yanhong Li; Jie Zhang; Jing Zhang; Shen Tang; Qiaodong Pan; Ting Hu; Yu Hou (International Biodeterioration & Biodegradation, 2024)

Pitch-based porous carbon via the solid–liquid synergistic oxidation of K2FeO4 for excellent electrocapacitive desalination - Xiang Bai; Lang Liu; Yakun Tang; Ting Liu; Xiaodong Zhou; Yue Zhang; Jingmei Liu; Caixia Zhu; Youyuan Xu; Fengyun Ma; Dianzeng Jia (Chemical Engineering Journal, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

A method for calculating generalized relaxation modulus for different rock types - Hailong Zhang; Yang Tang; Ting Ren; Junjie Wang; Seisuke Okubo (Bulletin of Engineering Geology and the Environment, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Matrine induces cardiotoxicity by promoting ferroptosis through the Nrf2 antioxidant system in H9c2 cells - Xi Wang; Zixiong Lin; Xinyi Tang; Minjuan Xie; Ting Li; Jie Zhou (Toxicology Letters, 2024)

ROS-mediated NRF2/p-ERK1/2 signaling-involved mitophagy contributes to macrophages activation induced by CdTe quantum dots - Na Liu; Ying Liang; Tingting Wei; Xiaoquan Huang; Ting Zhang; Meng Tang (Toxicology, 2024)

Developing meaningful water-energy-food-environment (WEFE) nexus indicators with stakeholders: An Upper White Nile case study - Annika Schlemm; Mark Mulligan; Ting Tang; Afnan Agramont; Jean Namugize; Enos Malambala; Ann van Griensven (Science of The Total Environment, 2024)

Investigating cultivation strategies for enhancing protein content in Auxenochlorella pyrenoidosa FACHB-5 - Qun Wei; Ting Yuan; Zhuang Li; Dan Zhao; Canmei Wang; Gairen Yang; Wangwang Tang; Xiangmeng Ma (Bioresource Technology, 2024)

A repertoire of intronic lariat RNAs reveals tissue-specific regulation and target mimicry potential in plants - Yong Zhang; Xiaotuo Zhang; Qi Tang; Lei Li; Ting Jiang; Yixiao Fang; Hong Zhang; Jixian Zhai; Guodong Ren; Binglian Zheng (Science China Life Sciences, 2024)

Streptomyces camelliae sp. nov., isolated from rhizosphere soil of Camellia oleifera Abel - Zheng Yaxi; Deng Aihua; Xu Xiaoxiao; Li Chenxi; Peng Yi; Tang Ting; Liu Jin; Ming Yiru; Mo Ping (Archives of Microbiology, 2024)

Photobiomodulation therapy moderates cancer cachexia-associated muscle wasting through activating PI3K/AKT/FoxO3a pathway - Yonghua Li; Yibing Chen; Yuan Liao; Ting Huang; Qing Tang; Chengsi He; Liu Xu; Haocai Chang; Hongsheng Li; Quentin Liu; Dongming Lai; Qing Xia; et al. (Apoptosis, 2024)

SNHG4-mediated PTEN destabilization confers oxaliplatin resistance in colorectal cancer cells by inhibiting ferroptosis - Si-qi Li; Wen-ting Xu; Yi-xin Yin; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Feng Lv; Li-ye Xie; Bang-li Hu (Apoptosis, 2024)

Non-targeted screening and photolysis transformation of tire-related compounds in roadway runoff - Jinfan Chen; Ting Tang; Yanxi Li; Rui Wang; Xingcai Chen; Dehao Song; Xiaodong Du; Xueqin Tao; Jiangmin Zhou; Zhi Dang; Guining Lu (Science of The Total Environment, 2024)

Quantitative proteomic analysis reveals the mechanism and key esterase of β-cypermethrin degradation in a bacterial strain from fermented food - Chuanning Peng; Jie Tang; Xuerui Zhou; Hu Zhou; Yingyue Zhang; Su Wang; Wanting Wang; Wenliang Xiang; Qing Zhang; Xuan Yu; Ting Cai (Pesticide Biochemistry and Physiology, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Explaining citizens’ plastic reduction behavior with an extended theory of planned behavior model: An empirical study in Switzerland - Bairong Wang; Ting Tang; Elvira Kaspar; Yong Li (Journal of Environmental Management, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Curcumin attenuates aflatoxin B1-induced ileum injury in ducks by inhibiting NLRP3 inflammasome and regulating TLR4/NF-κB signaling pathway - Hang Pan; Ting Hu; Ying He; Gaolong Zhong; Shaofeng Wu; Xuanxuan Jiang; Gan Rao; Yanli You; Zhiyan Ruan; Zhaoxin Tang; Lianmei Hu (Mycotoxin Research, 2024)

Characteristics and generation mechanisms of anticyclonic eddies, cyclonic eddies and dipole eddies in the Mozambique Channel - Ting Huang; Feng Zhou; Xiao Ma; Dingyong Zeng; Yong Tang; Yunlong Ma; Andre Emidio Raul; Ruibin Ding; Jorge Mario Mafuca; Ruijie Ye; Daji Huang (Frontiers in Marine Science, 2024)
The discovery of cyclonic and dipole eddies in the Mozambique Channel (MC) indicates that the understanding of the mesoscale eddy characteristics in the MC is incomplete. The distributions of anticyclonic, cyclonic, and dipole eddies along the MC were elucidated in this study using satellite observations. It was observed that these eddies exhibit a preference for emergence and movement in the western MC. The occurrence frequencies of anticyclonic and cyclonic eddies are four and three times per year, respectively, in the narrowest section of the MC. In contrast, the frequency of mesoscale eddies reaches its peak at nine times per year in the central region of the MC. The occurrence of dipole eddies also reaches its peak twice per year in the middle MC. Dipole eddies are more prevalent in the MC and exhibit larger dimensions and shorter lifespans compared to anticyclonic and cyclonic eddies. Mesoscale eddies, which traverse the narrowest section of the MC and propagate southward, are predominantly generated within the western Comoros Basin due to barotropic instability. The southward branch of the Northeast Madagascar Current (NEMC) plays a crucial role in transporting these eddies to the middle MC. The eastern middle MC is also a generation site for mesoscale eddies in addition to the Comoros Basin, where cyclonic eddies are generated twice per year. These cyclonic eddies are also generated due to barotropic instability.

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Associations between community green view index and fine particulate matter from Airboxes - Jia-Hong Tang; Ying-Jhen Huang; Ping-Hsien Lee; Yu-Ting Lee; Yu-Chun Wang; Ta-Chien Chan (Science of The Total Environment, 2024)

Low-dose cadmium telluride quantum dots trigger M1 polarization in macrophages through mTOR-mediated transcription factor EB activation - Tingting Wei; Na Liu; Yongshuai Yao; Xiaoquan Huang; Zhihui Wang; Tianshu Wu; Ting Zhang; Yuying Xue; Meng Tang (NanoImpact, 2024)

Integrated ultrastructural, physiological, transcriptomic, and metabolomic analysis uncovers the mechanisms by which nicotinamide alleviates cadmium toxicity in Pistia stratiotes L. - Xiong Li; Na Hu; Yanshuang Li; Haisheng Tang; Xumei Huang; Ting Yang; Jianchu Xu (Journal of Hazardous Materials, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Machine-learning-aided prediction and engineering of nitrogen-containing functional groups of biochar derived from biomass pyrolysis - Lijian Leng; Xinni Lei; Naif Abdullah Al-Dhabi; Zhibin Wu; Zequn Yang; Tanghao Li; Weijin Zhang; Wei Liu; Hao Zhan; Haoyi Peng; Wangwang Tang; Ting Xiong; et al. (Chemical Engineering Journal, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Land use, stratified wastewater and sediment, and microplastic attribute factors jointly influence the microplastic prevalence and bacterial colonization patterns in sewer habitats - Jianfeng Ye; Yi Zhu; Hao Chen; Jianfei Tang; Xin Zhao; Xiaonan Sun; Jinxu Zhang; Yu Chen; Yali Guo; Ning Fang; Yaqin Tan; Ting Zhang (Science of The Total Environment, 2024)

Biodegradation of phenanthrene-Cr (VI) co-contamination by Pseudomonas aeruginosa AO-4 and characterization of enhanced degradation of phenanthrene - Liuyuan Tang; Jing Yang; Xiaona Liu; Lingke Kang; Wenjun Li; Ting Wang; Tianwei Qian; Bo Li (Science of The Total Environment, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Identification of lncRNA-miRNA-mRNA Networks in the Lenticular Nucleus Region of the Brain Contributes to Hepatolenticular Degeneration Pathogenesis and Therapy - Wenjie Hao; Wenming Yang; Yue Yang; Ting Cheng; Taohua Wei; Lulu Tang; Nannan Qian; Yulong Yang; Xiang Li; Hailin Jiang; Meixia Wang (Molecular Neurobiology, 2024)
Long non-coding RNAs (lncRNAs) are a recently discovered group of non-coding RNAs that play a crucial role in the regulation of various human diseases, especially in the study of nervous system diseases which has garnered significant attention. However, there is limited knowledge on the identification and function of lncRNAs in hepatolenticular degeneration (HLD). The objective of this study was to identify novel lncRNAs and determine their involvement in the networks associated with HLD. We conducted a comprehensive analysis of RNA sequencing (RNA-seq) data, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and computational biology to identify novel lncRNAs and explore their potential mechanisms in HLD. We identified 212 differently expressed lncRNAs, with 98 upregulated and 114 downregulated. Additionally, 32 differently expressed mRNAs were found, with 15 upregulated and 17 downregulated. We obtained a total of 1131 pairs of co-expressed lncRNAs and mRNAs by Pearson correlation test and prediction and annotation of the lncRNA-targeted miRNA-mRNA network. The differential lncRNAs identified in this study were found to be involved in various biological functions and signaling pathways. These include translational initiation, motor learning, locomotors behavior, dioxygenase activity, integral component of postsynaptic membrane, neuroactive ligand-receptor interaction, nuclear factor-kappa B (NF-κB) signaling pathway, cholinergic synapse, sphingolipid signaling pathway, and Parkinson’s disease signaling pathway, as revealed by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Six lncRNAs, including XR_001782921.1 ( P < 0.01), XR_ 001780581.1 ( P < 0.01), ENSMUST_00000207119 ( P < 0.01), XR_865512.2 ( P < 0.01), TCONS_00005916 ( P < 0.01), and TCONS_00020683 ( P < 0.01), showed significant differences in expression levels between the model group and normal group by RT-qPCR. Among these, four lncRNAs (TCONS_00020683, XR_865512.2, XR_001780581.1, and ENSMUST00000207119) displayed a high degree of conservation. This study provides a unique perspective for the pathogenesis and therapy of HLD by constructing the lncRNA-miRNA-mRNA network. This insight provides a foundation for future exploration in this field.

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Mechanisms of oxidative response during biodegradation of malathion by S. oneidensis MR-1 - Qiaodong Pan; Yanhong Li; Jing Zhang; Ting Hu; Yu Hou; Shen Tang (Environmental Science and Pollution Research, 2024)
Malathion, an extensively used organophosphorus pesticide, poses a high potential risk of toxicity to humans and the environment. Shewanella (S.) oneidensis MR-1 has been proposed as a strain with excellent bioremediation capabilities, capable of efficiently removing a wide range of hard-to-degrade pollutants. However, the physiological and biochemical response of S. oneidensis MR-1 to malathion is unknown. Therefore, this study aimed to examine how S. oneidensis MR-1 responds physiologically and biochemically to malathion while also investigating the biodegradation properties of the pesticide. The results showed that the 7-day degradation rates of S. oneidensis MR-1 were 84.1, 91.6, and 94.0% at malathion concentrations of 10, 20, and 30 mg/L, respectively. As the concentration of malathion increased, superoxide dismutase and catalase activities were inhibited, leading to a significant rise in malondialdehyde content. This outcome can be attributed to the excessive production of reactive oxygen species (ROS) triggered by malathion stress. In addition, ROS production stimulates the secretion of soluble polysaccharides, which alleviates oxidative stress caused by malathion. Malathion-induced oxidative damage further exacerbated the changes in the cellular properties of S. oneidensis MR-1. During the initial stages of degradation, the cell density and total intracellular protein increased significantly with increasing malathion exposure. This can be attributed to the remarkable resistance of S. oneidensis MR-1 to malathion. Based on scanning electron microscopy observations, continuous exposure to contaminants led to a reduction in biomass and protein content, resulting in reduced cell activity and ultimately leading to cell rupture. In addition, this was accompanied by a decrease in Na + /K + - ATPase and Ca 2+ /Mg 2+ -ATPase levels, suggesting that malathion-mediated oxidative stress interfered with energy metabolism in S. oneidensis MR-1. The findings of this study provide new insights into the environmental risks associated with organophosphorus pesticides, specifically malathion, and their potential for bioremediation. Graphical Abstract

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Identification and characterization of β3 integrin in Crassostrea hongkongensis - Lei Tang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Pathogen-induced methylglyoxal negatively regulates rice bacterial blight resistance by inhibiting OsCDR1 protease activity - Zheng-Wei Fu; Jian-Hui Li; Xiang Gao; Shi-Jia Wang; Ting-Ting Yuan; Ying-Tang Lu (Molecular Plant, 2024)

A Chinese longitudinal maternity cohort study (2013–2021) on intrahepatic cholestasis phenotypes: Risk associations from environmental exposure to adverse pregnancy outcomes - Haitong Zhe Sun; Haiyang Tang; Jing Fang; Haizhen Dai; Huan Zhao; Siyuan Xu; Qingyi Xiang; Yijia Tian; Yurong Jiao; Ting Luo; Meishuang Huang; Jia Shu; et al. (Journal of Hazardous Materials, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Toxicity mechanism of engineered nanomaterials: Focus on mitochondria - Yongshuai Yao; Ting Zhang; Meng Tang (Environmental Pollution, 2024)

High-throughput absolute quantification sequencing reveals the adaptive succession and assembly pattern of plastisphere communities in municipal sewer systems: Influence of environmental factors and microplastic polymer types - Jianfeng Ye; Yi Zhu; Hao Chen; Xin Zhao; Jianfei Tang; Jinxu Zhang; Yu Chen; Yali Guo; Yaqin Tan; Ting Zhang (Environmental Pollution, 2024)

Design of D-A conjugated polymers for simultaneous selective bond breaking/formation and syngas production under visible light illumination - Guoen Tang; Guanhui Liu; Ting Song; Xiayi (Eric) Hu; Bei Long; Guo-Jun Deng (Chemical Engineering Journal, 2024)

Continuous thermophilic composting of distilled grain waste improved organic matter stability and succession of bacterial community - Shi-Peng Wang; Zhao-Yong Sun; Ming-Zhe An; Ting-Ting Wang; Zi-Yuan Xia; Yue-Qin Tang (Bioresource Technology, 2024)

A novel method for in situ imaging of root exudates and labile elements reveals phosphorus deficiency-induced mobilization of rare earth elements in the rhizosphere of Phytolacca americana - Chong Liu; Ting-Xuan Ding; Antony van der Ent; Chang Liu; Jean Louis Morel; Catherine Sirguey; Wen-Shen Liu; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2024)

Key issues to consider toward an efficient constructed wetland-microbial fuel cell: the idea and the reality - Diaodiao Li; Yaqian Zhao; Dan Wei; Cheng Tang; Ting Wei (Environmental Science and Pollution Research, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

Breathing in danger: Unveiling the link between human exposure to outdoor PM2.5-bound polycyclic aromatic hydrocarbons and lung cancer risk in an urban residential area of China - Lord Famiyeh; Honghui Xu; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Hang Xiao; Lei Tong; Chunrong Jia; Qingjun Guo; Jun He (Science of The Total Environment, 2024)

Protein corona exacerbated inflammatory response in macrophages elicited by CdTe quantum dots - Na Liu; Ying Liang; Tingting Wei; Xiaoquan Huang; Ting Zhang; Meng Tang (NanoImpact, 2024)

Arsenic induced neurotoxicity in the brain of ducks: The potential involvement of the gut-brain axis - Shaofeng Wu; Gaolong Zhong; Qian Su; Ting Hu; Gan Rao; Tong Li; Yuhan Wu; Zhiyan Ruan; Hui Zhang; Zhaoxin Tang; Lianmei Hu (Journal of Trace Elements in Medicine and Biology, 2024)

Interaction between chromite and Mn(II/IV) under anoxic, oxic and anoxic-oxic conditions: Dissolution, oxidation and pH dependence - Ming Ao; Shengsheng Sun; Tenghaobo Deng; Jingjing Li; Ting Liu; Yetao Tang; Shizhong Wang; Rongliang Qiu (Journal of Environmental Management, 2024)

Bell pepper derived nitrogen-doped carbon dots as a pH-modulated fluorescence switching sensor with high sensitivity for visual sensing of 4-nitrophenol - Guoqiang Guo; Tingting Li; Ziyi Liu; Xinyu Luo; Ting Zhang; Siyuan Tang; Xu Wang; Da Chen (Food Chemistry, 2024)

Bisphenol a alternatives suppress human and rat aromatase activity: QSAR structure-activity relationship and in silico docking analysis - Miaomiao Xia; Jingyi Zheng; Sailin Chen; Yunbing Tang; Shaowei Wang; Zhongyao Ji; Ting Hao; Huitao Li; Linxi Li; Ren-shan Ge; Yi Liu (Food and Chemical Toxicology, 2024)

A bibliometric analysis of global research hotspots and progress on microplastics in soil‒plant systems - Pengxinyue Huang; Yanyan Zhang; Naseer Hussain; Ting Lan; Guangdeng Chen; Xiaoyan Tang; Ouping Deng; Chaorui Yan; Yang Li; Ling Luo; Wenyu Yang; Xuesong Gao (Environmental Pollution, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Development of a highly sensitive aptamer-based electrochemical sensor for detecting saxitoxin based on K3Fe(CN)6 regulated silver nanoparticles - Wei Zeng; Xuemei Tang; Ting Wu; Bingjun Han; Long Wu (Analytica Chimica Acta, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

Release of chromium from Cr(III)- and Ni(II)-substituted goethite in presence of organic acids: Role of pH in the formation of colloids and complexes - Shengsheng Sun; Tenghaobo Deng; Ming Ao; Yijun Mo; Jingjing Li; Ting Liu; Wenjun Yang; Chao Jin; Rongliang Qiu; Yetao Tang (Science of The Total Environment, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Experimental investigation of post-fire seismic behavior of reinforced high-strength concrete shear walls - Yu-Ye Xu; Ting-Ting Tang; Ming Liu; Jun-Qi Huang (Engineering Structures, 2023)

The REY geochemistry of phosphorites during metamorphism of the Haizhou Group, NW Yangtze Block, China - Xiqiang Liu; Haifeng Fan; Hongjie Zhang; Chaoyi Xiao; Haiying Yang; Ting Zhou; Yong Tang; Pengqiang Shang; Chuanwei Zhu; Hanjie Wen (Chemical Geology, 2023)

TBTA-D2Net: a novel hyperspectral image classification method based on triple-branch ternary-attention mechanism and Dense2Net - Ting Tang; Shengwei Zhang; Shaopeng Liu; Weihong Yan; Xin Pan (International Journal of Remote Sensing, 2023)

Long-term ozone exposure is negatively associated with estimated glomerular filtration rate in Chinese middle-aged and elderly adults - Yiqin Zhang; Chen Tang; Yuwen Liu; Hanxiang Jiang; Jiaosheng Lu; Zhonghua Lu; Liping Xu; Siyu Zhang; Lina Zhou; Jing Ye; Xianfa Xuan; Ting Wu; et al. (Chemosphere, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

Corrigendum to “Recombinant expression of an oriental river prawn anti-lipopolysaccharide factor gene in Pichia pastoris and its characteristic analysis” [Fish Shellfish Immunol. 98 (2020) 414–419] - Ting Tang; Jinlan Liu; Shuangshuang Li; Hongquan Li; Fengsong Liu (Fish & Shellfish Immunology, 2023)

Lithium impacts the function of hematopoietic stem cells via disturbing the endoplasmic reticulum stress and Hsp90 signaling - Yalin Liu; Yifan Zhao; Jiaojiao Wu; Ting Liu; MengKe Tang; Ye Yao; Peng Xue; Miao He; Yanyi Xu; Peng Zhang; Minghua Gu; Weidong Qu; et al. (Food and Chemical Toxicology, 2023)

Mercury chloride activates the IFNγ-IRF1 signaling in myeloid progenitors and promotes monopoiesis in mice - Mengke Tang; Yifan Zhao; Yue Zhai; Yufan Zhang; Yalin Liu; Ting Liu; Jiaojiao Wu; Leyi He; Ye Yao; Peng Xue; Miao He; Yanyi Xu; et al. (Environmental Pollution, 2023)

Long-term oral tribasic copper chloride exposure impedes cognitive function and disrupts mitochondrial metabolism by inhibiting mitophagy in rats - Wenlan Yu; Xiaoyue Chang; Jianzhao Liao; Jinwen Quan; Siying Liu; Ting He; Gaolong Zhong; Jilei Huang; Zhonghua Liu; Zhaoxin Tang (Environmental Pollution, 2023)

Size distribution and lung-deposition of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

In Silico and Expression Analysis of Papain-Like Cysteine Proteinases (PLCP) Genes in Vitis vinifera to Predict Their Involvement in Hormonal Signaling and Disease Resistance - Ting Zhao; Jing Yan; Ziyang Qu; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Journal of Plant Growth Regulation, 2023)

Probabilistic versus deterministic potential seasonal climate predictability under the perfect-model framework - Dejian Yang; Youmin Tang; Xiu-Qun Yang; Xiangzhou Song; Xiaoxiao Tan; Yanling Wu; Xiaoqin Yan; Ting Liu; Xuguang Sun (Climate Dynamics, 2023)

Long-term field translocation differentially affects arbuscular mycorrhizal and ectomycorrhizal trees in a sub-tropical forest - Ting Wu; David T Tissue; Wei Su; Xu Li; Shimin Yang; Xujun Liu; Yue Liu; Zhiyang Lie; Shuyidan Zhou; Ze Meng; Junhua Yan; Xuli Tang; et al. (Agricultural and Forest Meteorology, 2023)

NR1 Splicing Variant NR1a in Cerebellar Granule Neurons Constitutes a Better Motor Learning in the Mouse - Ting Tan; Linyan Jiang; Zhengxiao He; Xuejiao Ding; Xiaoli Xiong; Mingxi Tang; Yuan Chen; Yaping Tang (The Cerebellum, 2023)
As an excitatory neuron in the cerebellum, the granule cells play a crucial role in motor learning. The assembly of NMDAR in these neurons varies in developmental stages, while the significance of this variety is still not clear. In this study, we found that motor training could specially upregulate the expression level of NR1a, a splicing form of NR1 subunit. Interestingly, overexpression of this splicing variant in a cerebellar granule cell-specific manner dramatically elevated the NMDAR binding activity. Furthermore, the NR1a transgenic mice did not only show an enhanced motor learning, but also exhibit a higher efficacy for motor training in motor learning. Our results suggested that as a “junior” receptor, NR1a facilitates NMDAR activity as well as motor skill learning.

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Artificial neural network-based investigation on high-speed train-induced embankment vibration in frozen regions - Shuang Tian; Liang Tang; Ting Li; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2023)

Remediation of bensulfuron methyl polluted water and soil by Fe2O3/Fe3O4@C activating peroxymonosulfate: Chloride enhancement effect and phytotoxicity assessment - Xiaoyu Wang; Lu Tang; Ting Yang; Ying Shi; Fang Liu; Hongmei Jiang (Chemical Engineering Journal, 2023)

Wettability tunable conjugated microporous poly(aniline)s for long-term, rapid and ppb level sequestration of Hg(II) - Duanlian Tang; Minlei Yin; Xiaowei Du; Yuxin Duan; Jie Chen; Ting Qiu (Chemical Engineering Journal, 2023)

Donor-acceptor 2D polymer for simultaneous photocatalytic CO2 reduction and carbonylation reaction - Guoen Tang; Xiaoyan Huang; Ting Song; Nailiang Wang; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2023)

The use of immobilised bacteria cross-linked within magnetic alginate beads enhances the treatment of benzophenone-type UV filter chemicals by the SBR system - Sai Hung Lau; Ching-Lun Su; Ting-Yu Yu; YuYing Zhong; XinYuan Xu; Wann-Neng Jane; Yi-Tang Chang (Chemosphere, 2023)

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

Adverse effects of sulfamethoxazole on locomotor behavior and lipid metabolism by inhibiting acetylcholinesterase and lipase in Daphnia magna - Yuming Zhang; Wenjie Xiu; Miao Yan; Xinrui Guo; Zhihua Ni; Jihai Gu; Ting Tang; Fengsong Liu (Science of The Total Environment, 2023)

Nano zero-valent iron enhances the absorption and transport of chromium in rice (Oryza sativa L.): Implication for Cr risks management in paddy fields - Ting Liu; Zeting Guan; Jingjing Li; Ming Ao; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Tracing surface water pollution in China’s supply chain - Siao Sun; Megan Konar; Qiuhong Tang; Guangtao Fu; Chuanglin Fang; Jing Wang; Yong Ni; Ting Ma (Journal of Hydrology, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Oxidation of 1,3-diphenylguanidine (DPG) by goethite activated persulfate: Mechanisms, products identification and reaction sites prediction - Jinbin Lai; Ting Tang; Xiaodong Du; Rui Wang; Jiahao Liang; Dehao Song; Zhi Dang; Guining Lu (Environmental Research, 2023)

Potential antidepressant-like effects of N-3 polyunsaturated fatty acids through inhibition of endoplasmic reticulum stress - Mimi Tang; Ting Liu; Yanmei Shen; Lu Wang; Ying Xue; Tingyu Zhao; Kaiqiang Xie; Zhicheng Gong; Tao Yin (Psychopharmacology, 2023)

Identification of suitable tributaries to compensate fish habitat loss in dammed rivers using environmental DNA metabarcoding - Yuqing Lin; Tao Feng; Lei Tang; Hui Zhang; Jianyun Zhang; Qiuwen Chen; Shufeng He; Ting Li (Hydrobiologia, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Catalytic supercritical water oxidation of o-chloroaniline over Ru/rGO: Reaction variables, conversion pathways and nitrogen distribution - Mian Hu; Zhibing Li; Xiaotong Huang; Meiqi Chen; Zhong-Ting Hu; Suqin Tang; I-Ming Chou; Zhiyan Pan; Qi Wang; Junliang Wang (Chemosphere, 2023)

Optimal government subsidy scheme for lean-oriented innovation in the textile industry - Ting Chen; Xinxin Zhang; Juan Tang; Hailing Guo (Journal of Cleaner Production, 2023)

Physicochemical properties and in vitro digestion behavior of emulsion gels stabilized by rice bran protein aggregates: Effects of heating time and induction methods - Yongxue Luo; Kexin Wang; Rui Pan; Ting Li; Qingjie Sun; Chuanfen Pu; Wenting Tang (Food Research International, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

Exploring Consumer Behavior and Preferences toward White Shrimp in Taiwan - Hao-Tang Jhan; Hsin-Ta Lee; Kuo-Huan Ting; Wen-Hong Liu (Fishes, 2023)
This study identifies and explores the key factors and issues that influence Taiwanese consumer behavior and preferences when it comes to the consumption of white shrimp. It aims to increase consumer confidence in, and purchase intention for, private-brand white shrimp and to develop marketing strategies and models for farmers who operate a self-produced, self-sold model. This study adopted the Alphabet theory and EKB modeling to obtain a holistic picture of white shrimp purchase behavior and consumer preferences. A semi-questionnaire was conducted with 921 consumers of white shrimp between November 2020 and March 2021, of which 787 questionnaires were valid and used in this study. Our study revealed the following noteworthy points. Freshness and drug residue are the two main concerns of white shrimp purchasers. The results of the consumer study show the existence of statistically significant differences between the defined segments in terms of general characteristics, consumption habits and behavior, and motivation for product awareness and purchase intention, as well as determination of the option of obtaining white shrimp for consumption. Our findings suggest that there is a significant correlation between product awareness and purchase intention. This has a number of practical implications for the self-produced, self-sold aquaculture farmer. In particular, it highlights the importance of the following: 1. establishing connection and trust by business model innovation, 2. improving product image and value, 3. providing product safety information to increase purchase intention and willingness to pay, and 4. developing production and sale plans in response to market demand.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Risk analysis of people evacuation and its path optimization during tunnel fires using virtual reality experiments - Xiaochun Zhang; Linjie Chen; Junhao Jiang; Yixin Ji; Shuyang Han; Ting Zhu; Wenbin Xu; Fei Tang (Tunnelling and Underground Space Technology, 2023)

New insights into nitrogen control strategies in sewage sludge pyrolysis toward environmental and economic sustainability - Mian Hu; Jiajia Ma; Zhuoran Jiang; Junliang Wang; Zhiyan Pan; Zhong-Ting Hu; Suqin Tang; Ramon Beims; Chunbao Xu (Science of The Total Environment, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

A review on current progress of Raman-based techniques in food safety: From normal Raman spectroscopy to SESORS - Long Wu; Xuemei Tang; Ting Wu; Wei Zeng; Xiangwei Zhu; Bing Hu; Sihang Zhang (Food Research International, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Peroxymonosulfate and peroxydisulfate activation by fish scales biochar for antibiotics removal: Synergism of N, P-codoped biochar - Qingyun He; Chenhui Zhao; Lin Tang; Zhifeng Liu; Binbin Shao; Qinghua Liang; Ting Wu; Yuan Pan; Jiajia Wang; Yang Liu; Shehua Tong; Tianjue Hu (Chemosphere, 2023)

VviKFB07 F-box E3 ubiquitin ligase promotes stilbene accumulation by ubiquitinating and degrading VviCHSs protein in grape - Ting Zhao; Congbo Huang; Shengzhi Li; Mengqiong Jia; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Plant Science, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

MPA-capped CdTequantum dots induces endoplasmic reticulum stress-mediated autophagy and apoptosis through generation of reactive oxygen species in human liver normal cell and liver tumor cell - Ting Zhang; Jie Lu; Ying Yao; Yanting Pang; Xiaomeng Ding; Meng Tang (Environmental Pollution, 2023)

Enzyme-responsive microneedle patch for bacterial infection and accelerated healing of diabetic wounds - Shizhou Wu; Boquan Qin; Xiaofang Tang; Ting Cui; Shijiu Yin; Hongxian Dong; Yunjie Liu; Shu Deng; Hui Zhang; Guoying Feng; Huiqi Xie; Lei Lei (Chemical Engineering Journal, 2023)

Pressure melting of pore ice in frozen rock under compression - Ting Wang; Hailiang Jia; Qiang Sun; Tuo Lu; Liyun Tang; Yanjun Shen (Cold Regions Science and Technology, 2023)

A multi-model prediction system for ENSO - Ting Liu; Yanqiu Gao; Xunshu Song; Chuan Gao; Lingjiang Tao; Youmin Tang; Wansuo Duan; Rong-Hua Zhang; Dake Chen (Science China Earth Sciences, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

Generate a new crucian carp (Carassius auratus) strain without intermuscular bones by knocking out bmp6 - Youyi Kuang; Xianhu Zheng; Dingchen Cao; Zhipeng Sun; Guangxiang Tong; Huan Xu; Ting Yan; Shizhan Tang; Zhongxiang Chen; Tingting Zhang; Tan Zhang; Le Dong; et al. (Aquaculture, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Corrigendum to “Adaptive regulations of Nrf2 alleviates silver nanoparticles-induced oxidative stress-related liver cells injury” [Chemico-Biol. Interact. 369 (2023) 110287] - Menghao Guo; Wenli Zhang; Shuyan Niu; Mengting Shang; Xiaoru Chang; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Chemico-Biological Interactions, 2023)

Effects of four hormones on the mitigation of ovarian damage in tilapia (Oreochromis niloticus) after copper and cadmium exposure - Yijie Wu; Ting Huang; Xin Yan; Jun Xiao; Zhirui Ma; Liming Luo; Liting Chen; Jinling Cao; Zhanyang Tang; Xinxian Wei; Fuyan Chen; Yu Zhu; et al. (Aquatic Toxicology, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Whole genome sequencing and transcriptomics-based characterization of a novel β-cypermethrin-degrading Gordonia alkanivorans GH-1 isolated from fermented foods - Xuerui Zhou; Jie Tang; Su Wang; Yingyue Zhang; Hong Ye; Qing Zhang; Wenliang Xiang; Ting Cai; Chaoyi Zeng (Chemosphere, 2023)

Identification and degradation of structural extracellular polymeric substances in waste activated sludge via a polygalacturonate-degrading consortium - Zhi-Yi Hu; Yi-Peng Lin; Qing-Ting Wang; Yi-Xin Zhang; Jie Tang; Si-Di Hong; Kun Dai; Shuai Wang; Yong-Ze Lu; Mark C.M. van Loosdrecht; Jianrong Wu; Raymond Jianxiong Zeng; et al. (Water Research, 2023)

Flavonoid accumulation modulates the responses of cassava tuberous roots to postharvest physiological deterioration - Feifei An; Mengjia Cui; Ting Chen; Cheng Cheng; Zhu Liu; Xiuqin Luo; Jingjing Xue; Yanqiong Tang; Jie Cai; Songbi Chen (Postharvest Biology and Technology, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Environmental fate of microplastics in an urban river: Spatial distribution and seasonal variation - Ting Li; Kai Liu; Rui Tang; Jun-Rong Liang; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Correction to: Arsenic Trioxide Triggers Mitochondrial Dysfunction, Oxidative Stress, and Apoptosis via Nrf 2/Caspase 3 Signaling Pathway in Heart of Ducks - Gan Rao; Gaolong Zhong; Ting Hu; Shaofeng Wu; Jiajia Tan; Xiaoyong Zhang; Riming Huang; Zhaoxin Tang; Lianmei Hu (Biological Trace Element Research, 2023)

Investigation of the nephrotoxicity of 2,6-dichloro-1,4-benzoquinone disinfection by-product in mice through a 28-day toxicity test - Ting Liu; Jun Wang; Xinyue Dang; Siyu Wan; Xi Luo; Wen Tang; Haiying Du; Minghua Jin; Juan Li; Jinhua Li (Toxicology, 2023)

Considerable role of urban functional form in low-carbon city development - Ting Lan; Guofan Shao; Zhibang Xu; Lina Tang; Hesong Dong (Journal of Cleaner Production, 2023)

Preventive effect of Ya'an Tibetan tea on obesity in rats fed with a hypercaloric high-fat diet revealed by gut microbiology and metabolomics studies - Ye Yuan; Jingliu He; Ming Tang; Hong Chen; Ting Wei; Bin Zhang; Dawei Liang; Xuqiang Nie (Food Research International, 2023)

Identification of a key locus, qNL3.1, associated with seed germination under salt stress via a genome-wide association study in rice - Chengfang Zhan; Peiwen Zhu; Yongji Chen; Xinyi Chen; Kexin Liu; Shanshan Chen; Jiaxiao Hu; Ying He; Ting Xie; Shasha Luo; Zeyuan Yang; Sunlu Chen; et al. (Theoretical and Applied Genetics, 2023)
Key message Two causal OsTTL and OsSAPK1 genes of the key locus qNL3.1 significantly associated with seed germination under salt stress were identified via a genome-wide association study, which could improve rice seed germination under salt stress. Abstract Rice is a salt-sensitive crop, and its seed germination determines subsequent seedling establishment and yields. In this study, 168 accessions were investigated for the genetic control of seed germination under salt stress based on the germination rate (GR), germination index (GI), time at which 50% germination was achieved ( T 50 ) and mean level (ML). Extensive natural variation in seed germination was observed among accessions under salt stress. Correlation analysis showed significantly positive correlations among GR, GI and ML and a negative correlation with T 50 during seed germination under salt stress. Forty-nine loci significantly associated with seed germination under salt stress were identified, and seven of these were identified in both years. By comparison, 16 loci were colocated with the previous QTLs, and the remaining 33 loci might be novel. qNL3.1 , colocated with qLTG-3 , was simultaneously identified with the four indices in two years and might be a key locus for seed germination under salt stress. Analysis of candidate genes showed that two genes, the similar to transthyretin-like protein OsTTL and the serine/threonine protein kinase OsSAPK1 , were the causal genes of qNL3.1 . Germination tests indicated that both Osttl and Ossapk1 mutants significantly reduced seed germination under salt stress compared to the wild type. Haplotype analysis showed that Hap.1 of OsTTL and Hap.1 of OsSAPK1 genes were excellent alleles, and their combination resulted in high seed germination under salt stress. Eight accessions with elite performance of seed germination under salt stress were identified, which could improve rice seed germination under salt stress.

Effects of exogenous carbon and nitrification inhibitors on denitrification rate, product stoichiometry and nirS/nirK-type denitrifiers in a calcareous soil: evidence from 15 N anaerobic microcosm assays - Ting Lan; Mengxiao Li; Xiaoqian He; Junji Yuan; Minghua Zhou; Xiaoyan Tang; Yanyan Zhang; Yang Li; Zhaonan Tian; Xuesong Gao (Journal of Soils and Sediments, 2023)

Arsenic Trioxide Triggers Mitochondrial Dysfunction, Oxidative Stress, and Apoptosis via Nrf 2/Caspase 3 Signaling Pathway in Heart of Ducks - Gan Rao; Gaolong Zhong; Ting Hu; Shaofeng Wu; Jiajia Tan; Xiaoyong Zhang; Riming Huang; Zhaoxin Tang; Lianmei Hu (Biological Trace Element Research, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

Construction of a novel S-scheme heterojunction piezoelectric photocatalyst V-BiOIO3/FTCN and immobilization with floatability for tetracycline degradation - Ting Wu; Qinghua Liang; Lin Tang; Jialin Tang; Jiajia Wang; Binbin Shao; Shanxi Gong; Qingyun He; Yuan Pan; Zhifeng Liu (Journal of Hazardous Materials, 2023)

Complex plant protein prepared from rice protein and pea protein: Improve the thermal stability of betanin - Ting Hu; Jun Chen; Xuemei He; Yayuan Tang; Jian Sun; Chengmei Liu; Taotao Dai (Food Research International, 2023)

Degradation mechanism and pathway of tetracycline in milk by heterojunction N-TiO2-Bi2WO6 film under visible light - Yuedeng Tang; Ting Li; Wenxuan Xiao; Zitong Huang; Huicui Wen; Wenbei Situ; Xianliang Song (Food Chemistry, 2023)

Rapid screening of antioxidant from natural products by AAPH-Incubating HPLC-DAD-HR MS/MS method: A case study of Gardenia jasminoides fruit - Guo-Dong Zhuang; Wen-Ting Gu; Shu-Hong Xu; Dong-Min Cao; Si-Min Deng; Yong-Sheng Chen; Shu-Mei Wang; Dan Tang (Food Chemistry, 2023)

Whole genome sequencing exploitation analysis of dibutyl phthalate by strain Stenotrophomonas acidaminiphila BDBP 071 - Yingyue Zhang; Jie Tang; Min Wu; Xuerui Zhou; Su Wang; Hong Ye; Wenliang Xiang; Qing Zhang; Ting Cai (Food Bioscience, 2023)

Recent advances on electrocatalytic CO2 reduction to resources: Target products, reaction pathways and typical catalysts - Yaru Lei; Zheng Wang; Ai Bao; Xiaolong Tang; Xiubing Huang; Honghong Yi; Shunzheng Zhao; Ting Sun; Junyi Wang; Fengyu Gao (Chemical Engineering Journal, 2023)

Application of regression and artificial neural network analysis of Red-Green-Blue image components in prediction of chlorophyll content in microalgae - Doris Ying Ying Tang; Kit Wayne Chew; Huong-Yong Ting; Yuk-Heng Sia; Francesco G. Gentili; Young-Kwon Park; Fawzi Banat; Alvin B. Culaba; Zengling Ma; Pau Loke Show (Bioresource Technology, 2023)

Detecting the tipping point between heat source and sink landscapes to mitigate urban heat island effects - Ting Liu; Shuai Ouyang; Mengmeng Gou; Hailiang Tang; Yue Liu; Liang Chen; Pifeng Lei; Zhonghui Zhao; Chuanhong Xu; Wenhua Xiang (Urban Ecosystems, 2023)

Phosphorus mediated rhizosphere mobilization and apoplast precipitation regulate rare earth element accumulation in Phytolacca americana - Chong Liu; Ting-Xuan Ding; Wen-Shen Liu; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Anaerobic methane oxidation coupled to arsenate reduction in paddy soils: Insights from laboratory and field studies - Yujie Zhou; Ting Guo; Williamson Gustave; Zhaofeng Yuan; Jingxuan Yang; Dan Chen; Xianjin Tang (Chemosphere, 2023)

Pulmonary hazard identifications of Graphene family nanomaterials: Adverse outcome pathways framework based on toxicity mechanisms - Xiaomeng Ding; Yuepu Pu; Meng Tang; Ting Zhang (Science of The Total Environment, 2023)

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

The DNA damage potential of quantum dots: Toxicity, mechanism and challenge - Yongshuai Yao; Ting Zhang; Meng Tang (Environmental Pollution, 2023)

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

Sink-source unbalance leads to abnormal partitioning of biomass and nitrogen in rice under extreme heat stress: An experimental and modeling study - Ting Sun; Bing Liu; Toshihiro Hasegawa; Zhiyi Liao; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu (European Journal of Agronomy, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Subcutaneous injection of a bortezomib-loaded thermosensitive hydrogel for the treatment of multiple myeloma - Ying Qu; Bingyang Chu; Kun Shi; Xue Wei; Peipei Yang; Mengran Chen; Minghai Tang; Shiqian Li; Fangfang Wang; Xijing Yang; Yuhuan Zheng; Ting Niu; et al. (Chemical Engineering Journal, 2023)

Donor-acceptor organic polymer with sulfur bridge for superior photocatalytic CO2 reduction to CH4 under visible light illumination - Guoen Tang; Jingrong Li; Yanling Lu; Ting Song; Shiheng Yin; Guojiang Mao; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

Adaptive regulations of Nrf2 alleviates silver nanoparticles-induced oxidative stress-related liver cells injury - Menghao Guo; Wenli Zhang; Shuyan Niu; Mengting Shang; Xiaoru Chang; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Chemico-Biological Interactions, 2023)

Sodium acetate ameliorates cisplatin-induced kidney injury in vitro and in vivo - Jun-Yao Zheng; Shao-Chuan Wang; Sheau-Chung Tang; I-Lun Hsin; Yu-Ting Kang; Chih-Ting Hsu; Chu-Chyn Ou; Jiunn-Liang Ko (Chemico-Biological Interactions, 2023)

Magnetic covalent organic framework for the adsorption of silver nanoparticles and recycled as surface-enhanced Raman substrate and high-efficiency catalysts for 4-nitrophenol degradation - Zhijuan Zheng; Ke Xu; Feifei Lu; Baohua Zhong; Lijun You; Weijie Xiong; Ting Tang; Shaoyun Wang (Environmental Science and Pollution Research, 2022)

Metabolism toxicity and susceptibility of decabromodiphenyl ether (BDE-209) exposure on BRL cells with insulin resistance - Guanghua Mao; Junjie Tang; Taotao Liao; Xiaoxiang Shi; FangYuan Dong; Weiwei Feng; Yao Chen; Ting Zhao; Xiangyang Wu; Liuqing Yang (Environmental Science and Pollution Research, 2022)

The predictability study of the two flavors of ENSO in the CESM model from 1881 to 2017 - Ting Liu; Xunshu Song; Youmin Tang (Climate Dynamics, 2022)
In this study, we evaluated the predictability of the two flavors of the El Niño Southern Oscillation (ENSO) based on a long-term retrospective prediction from 1881 to 2017 with the Community Earth System Model. Specifically, the Central-Pacific (CP) ENSO has a more obvious Spring Predictability Barrier and lower deterministic prediction skill than the Eastern-Pacific (EP) ENSO. The potential predictability declines with lead time for both the two flavors of ENSO, and the EP ENSO has a higher upper limit of the prediction skill as compared with the CP ENSO. The predictability of the two flavors of ENSO shows distinct interdecadal variation for both actual skill and potential predictability; however, their trends in the predictability are not synchronized. The signal component controls the seasonal and interdecadal variations of predictability for the two flavors of ENSO, and has larger contribution to the CP ENSO than the EP ENSO. There is significant scope for improvement in predicting the two flavors of ENSO, especially for the CP ENSO.

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Retraction Note to: Mercury isotope constraints on the sources of metals in the Baiyangping Ag-Cu-Pb-Zn polymetallic deposits, SW China - Yongyong Tang; Runsheng Yin; Ruizhong Hu; Guangyi Sun; Zhichao Zou; Ting Zhou; Xianwu Bi (Mineralium Deposita, 2022)

Genome-Wide Identification and Expression Analysis of Thioredoxin (Trx) Genes in Seed Development of Vitis vinifera - Jingru Zhang; Ting Zhao; Fengdan Yan; Ling Wang; Yujin Tang; Yuejin Wang; Chaohong Zhang (Journal of Plant Growth Regulation, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Towards less invasive molecular diagnostics for endometrial cancer: massively parallel sequencing of endometrial lavage specimens in women attending for an office hysteroscopy - Angel Chao; Kai-Yun Wu; Chiao-Yun Lin; Yun-Shien Lee; Huei-Jean Huang; Yun-Hsin Tang; Cindy Hsuan Weng; An-Shine Chao; Ting-Chang Chang; Chyong-Huey Lai; Ren-Chin Wu (Journal of Molecular Medicine, 2022)

The Potential Compatibility of Designating Offshore Wind Farms within Wider Marine Protected Areas—Conservation of the Chinese White Dolphin Regarding Fishers’ Perception - Hao-Tang Jhan; Hsin-Ta Lee; Kuo-Huan Ting (Fishes, 2022)
The population of the Chinese white dolphin along Taiwan’s west coast is under a range of threats. The designation of marine protected areas (MPA) is urgently required for their protection. However, conflicts between specific species conservation and fishing rights mean that the success of such a designation relies on the fishers’ perceptions and awareness of an MPA. Designating offshore wind farms within MPAs can be a mechanism for minimizing conflicts between fisheries and conservation. The purpose of this study is to examine the potential for designating an offshore wind farm within an MPA for Chinese white dolphin conservation by exploring the attitudes of local fishers. This study used face-to-face questionnaires. The results show that the main challenges are conflicts of interest, insufficient science-based information, and inadequate law enforcement. Offshore wind farms could be a way to maximize the benefits for different stakeholders and positively impact the marine environment and ecosystem. This study makes feasible recommendations on how to improve conservation, promote renewable energy, and encourage sustainable fisheries.

Occurrence characteristics and health risk assessment of per- and polyfluoroalkyl substances from water in residential areas around fluorine chemical industrial areas, China - Jiaxi Tang; Yongle Zhu; Yu Li; Biao Xiang; Ting Tan; Linyou Lv; Qing Luo (Environmental Science and Pollution Research, 2022)

Decreasing magnitude of soil erosion along vegetation succession on sloping farmland in the Loess Plateau of China: 5 years field monitoring evidence - Yue Liang; Ju-ying Jiao; Bing-zhe Tang; Bin-ting Cao; Hang Li (Journal of Mountain Science, 2022)

Characteristics and diversity of endophytic bacteria in Panax notoginseng under high temperature analysed using full-length 16S rRNA sequencing - Zhenting Liang; Xianjing Lin; Yiqun Liao; Ting Tang (Archives of Microbiology, 2022)

Triple-branch ternary-attention mechanism network with deformable 3D convolution for hyperspectral image classification - Ting Tang; Jiangping Liu; Xiaoling Luo; Xiaojing Gao; Xin Pan (International Journal of Remote Sensing, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Prediction of drought/flood intensities based on a 500-year time series in three different climate provinces of China - Yu Peng; Zhaohua Wang; Yixin Cui; Yali Su; Yiyun Tang; Shiqian Luo; Lianlin Liu; Yanqiu Zhou; Jihui Dong; Wentao Wang; Xiang Li; Jiaxin Shang; et al. (Regional Environmental Change, 2022)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Potential vorticity perspective of the genesis of a Tibetan Plateau vortex in June 2016 - Guoxiong Wu; Yiqiong Tang; Bian He; Yimin Liu; Jiangyu Mao; Tingting Ma; Ting Ma (Climate Dynamics, 2022)
At midnight on 27–28 June 2016, a Tibetan Plateau (TP) Vortex (TPV) generated over the western TP that subsequently caused a downstream record-breaking rainstorm and extremely severe natural disaster. Based on reanalysis data and satellite imagery, this study investigates the formation of this TPV from a potential vorticity (PV) perspective. Results show that, in late June 2016, a remarkable circulation anomaly occurred over the TP and its peripheral area, with easterly flow in the middle and lower troposphere developing in the subtropical zone, replacing the normal westerly flow there. Its forefront merged with the southwesterly flow from the west and penetrated and converged over the western TP where the surface was warmer than normal, forming a low-level jet and downward slantwise isentropic surfaces in-situ. When the air parcel slid down the slantwise isentropic surface, its vertical relative vorticity developed owing to slantwise vorticity development associated with PV restructuring. At the same time, the penetrating southwesterly flow brought abundant water vapor to the western TP and induced increasing sub-cloud entropy and air ascent there. Low-layer cloud formed and the cloud liquid water content increased. The strong latent heat that was released in association with the formation of cloud produced strong diabatic heating near 400 hPa at night and strong PV generation below. The normal diurnal variation was interrupted and the vortex was generated near the surface. These results demonstrate that, against a favorable circulation background, both adiabatic and diabatic PV processes are crucial for TPV genesis.

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

Cracking and Photo-Oxidation of Polyoxymethylene Degraded in Terrestrial and Simulated Marine Environments - Chih-Cheng Tang; Ying-Ting Chen; Yi-Ming Zhang; Huey-Ing Chen; Peter Brimblecombe; Chon-Lin Lee (Frontiers in Marine Science, 2022)
Marine plastic debris is an environmental problem, and its degradation into microplastics (1-5000 μm) introduces them into the food chain. In this study, small polyoxymethylene (global production ~3000 Tg per year) pellets were exposed in terrestrial and simulated marine environments to heat and light, resulting in cracking during decay with increasing IR absorption (OH-bonds). Furthermore, sunlight over three years reduced pellet mass and diameter (~10% and ~40%), initially yielding 100-300 μm fragments. Changes under UV irradiation were smaller as it could not penetrate into particle interiors. Characteristic spacing of surface striations (100-300 µm) initiated radial cracks to pellet interiors, and breakdown ultimately meant 95% of particles were <300 µm, which are potentially incorporated in marine turbidites.

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Time dependency for generalized relaxation compliance of rock - Hailong Zhang; Yang Tang; Ting Ren; Seisuke Okubo; Shoujian Peng (Bulletin of Engineering Geology and the Environment, 2022)

Application of Bone Marrow Mesenchymal Stem Cells Effectively Eliminates Endotoxemia to Protect Rat from Acute Liver Failure Induced by Thioacetamide - Ting Jiang; Geng Xia; Bo Yang; Hong-wei Zhang; Yue-shan Yin; Cheng-wei Tang; Jin-hui Yang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Endotoxemia is related to worse clinical outcomes in acute liver failure (ALF), but its management remains unsatisfactory. In this study, we aimed to assess whether the application of bone marrow mesenchymal stem cells (BMSCs) could eliminate endotoxemia and protect rats against ALF induced by thioacetamide (TAA). Methods: BMSCs were isolated from rats and identified by the specific morphology, differentiation potential, and surface markers. The optimal dose of TAA for this study was explored and TAA-induced ALF rats were randomized to three groups: the normal control group (Saline), ALF group (TAA + Saline), and BMSCs-treated group (TAA + BMSCs). The intestinal migration and differentiation of BMSCs was tracked in vivo , and intestinal permeability, endotoxin and inflammatory cytokines, histology, and mortality were analyzed. Moreover, we added the inhibitor of the PI3K/AKT/mTOR signaling pathway into the co-culture system of BMSCs with enterocytes and then performed CK and Villin expression experiments to assess the role of PI3K/AKT/mTOR signal pathway in the intestinal differentiation of BMSCs. Results: BMSCs migrated to the intestinal injury sites and differentiated into enterocytes, intestinal permeability was decreased compared with the ALF group. The higher expression of endotoxin and inflammatory cytokines were reversed after BMSCs transplantation in rats with ALF. Mortality and intestinal lesion were significantly decreased. Blocking the PI3K/AKT/mTOR signal pathway inhibited BMSCs’ intestinal differentiation in vitro . Conclusion: BMSCs can eliminate endotoxemia and reduce mortality in rats with ALF, and the PI3K/AKT/mTOR signal pathway is involved in intestinal differentiation. BMSCs transplantation could be a potential candidate for the treatment of endotoxemia in ALF.

RETRACTED ARTICLE: Mercury isotope constraints on the sources of metals in the Baiyangping Ag-Cu-Pb-Zn polymetallic deposits, SW China - Yongyong Tang; Runsheng Yin; Ruizhong Hu; Guangyi Sun; Zhichao Zou; Ting Zhou; Xianwu Bi (Mineralium Deposita, 2022)

Optimizing Fertilizer Management Based on Controlled-Release Fertilizer to Improve Yield, Quality, and Reduce Fertilizer Application on Apples - Junyin Li; Yan Liu; Yafu Tang; Junfei Shao; Ting Xu; Ronghui Ma; Yuanmao Jiang; Dongdong Cheng (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Vitamin D mediates the association between acrylamide hemoglobin biomarkers and obesity - Ting Yin; Fang Xu; Shi Shi; Shengen Liao; Xiaosu Tang; Haifeng Zhang; Yanli Zhou; Xinli Li (Environmental Science and Pollution Research, 2022)

Vitamin D mediates the association between acrylamide hemoglobin biomarkers and obesity - Ting Yin; Fang Xu; Shi Shi; Shengen Liao; Xiaosu Tang; Haifeng Zhang; Yanli Zhou; Xinli Li (Environmental Science and Pollution Research, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Effect of exogenous abscisic acid (ABA) on the morphology, phytohormones, and related gene expression of developing lateral roots in ‘Qingzhen 1’ apple plants - Xiaoyun Zhang; Muhammad Mobeen Tahir; Shaohuan Li; Ting Tang; Jiangping Mao; Ke Li; Yun Shao; Weiwei Yang; Jianxin Niu; Dong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

The Effect of Manure Application on Arsenic Mobilization and Methylation in Different Paddy Soils - Su Yang; Weiwei Zhai; Xianjin Tang; Williamson Gustave; Zhaofeng Yuan; Ting Guo; Yingge Shu (Bulletin of Environmental Contamination and Toxicology, 2022)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Evaluation of toxic effects induced by arsenic trioxide or/and antimony on autophagy and apoptosis in testis of adult mice - Shaofeng Wu; Gaolong Zhong; Fang Wan; Xuanxuan Jiang; Zhaoxin Tang; Ting Hu; Gan Rao; Juan Lan; Riaz Hussain; Lixuan Tang; Hui Zhang; Riming Huang; et al. (Environmental Science and Pollution Research, 2021)

Whole-exome sequencing identified a novel mutation in CHM of a Chinese family - Hui Tang; Jun Mao; Jingjing Xiang; Minjuan Liu; Haibo Li; Ting Wang (Journal of Genetics, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Anti-inflammatory steroids from the fruits of Artocarpus heterophyllus - Yun-Yao Liu; Ting Wang; Rong-Xiang Yang; Hao-Xuan Tang; Lei Qiang; Yan-Ping Liu (Natural Product Research, 2021)

Hygrophorus russula complex (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Moreno Gabriel; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Magmatic-hydrothermal evolution of an unusual Mo-rich carbonatite: a case study using LA-ICP-MS fluid inclusion microanalysis and He–Ar isotopes from the Huangshui’an deposit, Qinling, China - Li Tang; Thomas Wagner; Tobias Fusswinkel; Shou-Ting Zhang; Bo Xu; Li-Hui Jia; Xin-Kai Hu (Mineralium Deposita, 2021)

Microwave-assisted high-efficiency degradation of methyl orange by using CuFe2O4/CNT catalysts and insight into degradation mechanism - Zhifeng Liu; Wei Zhang; Qinghua Liang; Jinhui Huang; Binbin Shao; Yang Liu; Yujie Liu; Qingyun He; Ting Wu; Jilai Gong; Ming Yan; Wangwang Tang (Environmental Science and Pollution Research, 2021)

Novel PET/CT tracers for targeted imaging of membrane receptors to evaluate cardiomyocyte apoptosis and tissue repair process in a rat model of myocardial infarction - Ting Sun; Lijiang Wei; Hua Tian; Wanlin Zhan; Hui Ma; Dahong Nie; Shilin Wang; Xin Chen; Ganghua Tang (Apoptosis, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Strategy for the advanced treatment of simulated tail water of dyeing wastewater based on a short-cut photocatalysis/algal degradation hybrid technology - Ting Huang; Xiaomin Tang; Shixin Zhang; Wei Wang; Jie Zhang; Xuemei Tan; Huaili Zheng (Environmental Science and Pollution Research, 2021)

A theoretical relationship between probabilistic relative operating characteristic skill and deterministic correlation skill in dynamical seasonal climate prediction - Dejian Yang; Youmin Tang; Xiu-Qun Yang; Dan Ye; Ting Liu; Tao Feng; Xiaoqin Yan; Xuguang Sun; Yaocun Zhang (Climate Dynamics, 2021)
Understanding the relationship between probabilistic and deterministic prediction skills is of important significance for the study of seasonal forecasting and verification. Based on the Brier skill score methodology, we have previously found a theoretical relationship between the probabilistic resolution skill and the deterministic correlation (i.e., anomaly correlation; AC) skill and a lack of necessary or consistent relationship between the probabilistic reliability skill and the deterministic skill in dynamical seasonal prediction. Here, we further theoretically investigate the relationship between the probabilistic relative operating characteristic (ROC) skill and the deterministic skill. The ROC measures the discrimination attribute of probabilistic forecast quality, another important attribute besides the resolution and reliability. With some simplified assumptions, we first derive theoretical expressions for the hit and false-alarm rates that are basic ingredients for the ROC curve, then demonstrate a sole dependence of the ROC curve on the AC, and finally analytically derive a relationship between the related ROC score and the AC. Such a theoretically derived ROC-AC relationship is further examined using dynamical models’ ensemble seasonal hindcasts, which is well verified. The finding here along with our previous findings implies that the discrimination and resolution attributes of probabilistic seasonal forecast skill are intrinsically equivalent to the corresponding deterministic skill, while the reliability appears to be the fundamental attribute of the probabilistic skill that differs from the deterministic skill, which constitutes an understanding of the fundamental similarities and difference between the two types of seasonal forecasting skills and predictability and can offer important implications for the study of seasonal forecasting and verification.

Smarcd1 Inhibits the Malignant Phenotypes of Human Glioblastoma Cells via Crosstalk with Notch1 - Yihao Zhu; Handong Wang; Maoxing Fei; Ting Tang; Wenhao Niu; Li Zhang (Molecular Neurobiology, 2021)
Smarcd1 is a component of an evolutionary conserved chromatin remodeling complex—SWI/SNF, which is involved in transcription factor recruitment, DNA replication, recombination, and repair. Suppression of the SWI/SNF complex required for cellular differentiation and gene regulation may be inducible for cell proliferation and tumorigenicity. However, the inhibitory role of Smarcd1 in human glioblastoma cells has not been well illustrated. Both U87 and U251 human glioblastoma cell lines were employed in the present study. The lentivirus-mediated gene knockdown and overexpression approach was conducted to determine the function of Smarcd1. The protein levels were tested by western blot, and the relative mRNA contents were detected by quantitative real-time PCR. Cell viability was tested by CCK-8 and colony-forming assay. Transwell assays were utilized to evaluate the motility and invasive ability. Flow cytometry was employed to analyze cell cycle and apoptosis. SPSS software was used for statistical analysis. Low expression of Smarcd1 was observed in glioblastoma cell lines and in patients with high-grade glioma. Importantly, the depletion of Smarcd1 promoted cell proliferation, invasion, and chemoresistance, whereas enhanced expression of Smarcd1 inhibited tumor-malignant phenotypes. Mechanistic research demonstrated that overexpression of Smarcd1 decreased the expression of Notch1, while knockdown of Notch1 increased the expression of Smarcd1 through Hes1 suppression. Hence, the crosstalk between Smarcd1 and Notch1, which formed a feedback loop, was crucial in regulation of glioblastoma malignant phenotypes. Furthermore, targeting Smarcd1 could be a potential strategy for human glioblastoma treatment.

Regulating CH4, N2O, and NO emissions from an alkaline paddy field under rice–wheat rotation with controlled release N fertilizer - Ting Lan; Heng Zhang; Yong Han; Ouping Deng; Xiaoyan Tang; Ling Luo; Jian Zeng; Guangdeng Chen; Changquan Wang; Xuesong Gao (Environmental Science and Pollution Research, 2021)

Abnormalities in hemispheric lateralization of intra- and inter-hemispheric white matter connections in schizophrenia - Dandan Li; Wenjing Tang; Ting Yan; Nan Zhang; Jie Xiang; Yan Niu; Bin Wang (Brain Imaging and Behavior, 2021)

Thiazole-based and thiazolidine-based protein tyrosine phosphatase 1B inhibitors as potential anti-diabetes agents - Kexin Chen; Xu Yao; Ting Tang; Li-Mei Chen; Can Xiao; Jing-Yi Wang; Hong-Fei Chen; Zhong-Xing Jiang; Yi Liu; Xing Zheng (Medicinal Chemistry Research, 2021)

Dolomitization of the Middle Ordovician Ma55 Sub-member of the Majiagou Formation and implications for hydrocarbon exploration in the northern Ordos Basin, NW China - Hua Liu; Pingzhou Shi; Hongming Tang; Zhenyu Wang; Ting Shang; Zhongjun Zhao; Longlong Li; Kaixuan Liu (Carbonates and Evaporites, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Current rice models underestimate yield losses from short‐term heat stresses - Ting Sun; Toshihiro Hasegawa; Bing Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu (Global Change Biology, 2021)
Crop production will likely face enormous challenges against the occurrences of extreme climatic events projected under future climate change. Heat waves that occur at critical stages of the reproductive phase have detrimental impacts on the grain yield formation of rice ( Oryza sativa ). Accurate estimates of these impacts are essential to evaluate the effects of climate change on rice. However, the accuracy of these predictions by crop models has not been extensively tested. In this study, we evaluated 14 rice growth models against four year phytotron experiments with four levels of heat treatments imposed at different times after flowering. We found that all models greatly underestimated the negative effects of heat on grain yield, suggesting that yield projections with these models do not reflect food shocks that may occur under short‐term extreme heat stress (SEHS). As a result, crop model ensembles do not help to provide accurate estimates of grain yield under heat stress. We examined the functions of grain‐setting rate response to temperature (TRF_GS) used in eight models and showed that adjusting the effective periods of TRF_GS improved the model performance, especially for models simulating accumulative daily temperature effects. For TRF_GS which uses daily maximum temperature averaged for the effective period, the models provided better grain yield estimates by using maximum temperatures averaged only when daily maximum temperatures exceeded the base temperature ( T base ). An alternative method based on heating‐degree days and stage‐dependent heat sensitivity parameters further decreased the prediction uncertainty of grain yield under heat stress, where stage‐dependent heat sensitivity was more important than heat dose for model improvement under SEHS. These results suggest the limitation of the applicability of existing rice models to variable climatic conditions and the urgent need for an alternative grain‐setting function accounting for the stage‐dependent heat sensitivity.

Purinergic signalling mediates the inhibitory effect of microglia on neuronal activity in the brain - Yu-Ting Dong; Yong Tang (Purinergic Signalling, 2020)

An extension of LDEO5 model for ENSO ensemble predictions - Yanqiu Gao; Ting Liu; Xunshu Song; Zheqi Shen; Youmin Tang; Dake Chen (Climate Dynamics, 2020)
This study provided an extension to the latest version of Lamont-Doherty Earth Observation (LDEO5) prediction system. First, an ensemble coupled data assimilation (CDA) system, based on the Ensemble Kalman Filter, was established. Both the Kaplan sea surface temperature (SST) data from January 1856 to December 2018 and the ECMWF twentieth century reanalysis (ERA-20C) wind data from January 1900 to February 2010 were assimilated for prediction initialization. Second, an ensemble prediction (EP) system was established using stochastic optimal perturbation that represented the uncertainty in the physical process. The assimilation experiments showed that assimilating multi-source data yielded better results than assimilating single-source data. The analyses of Niño3.4 SST anomalies and zonal wind stress (ZWS) anomalies were in good agreement with the observed counterparts, respectively. The root mean square errors of both Niño3.4 SST anomalies and ZWS anomalies were found to be significantly reduced, compared to the values obtained before assimilation. The modeled upper layer depth anomalies along the equator, and subsurface temperature anomalies in the Niño3.4 region were also found to be similar to the observed counterparts. A long-term ensemble hindcast was conducted using the EP system for the past 163 years, from January 1856 to December 2018. Results showed that the predictions initialized by assimilating multi-source data yielded best deterministic skill, reaching the international advanced level. A comparative analysis revealed that the EP system predicted the warm events well, followed by cold and neutral events.

Subcellular localization of the porcine deltacoronavirus nucleocapsid protein - Zhen Ding; Suxian Luo; Wang Gong; Leyi Wang; Nengshui Ding; Jun Chen; Jiajia Chen; Ting Wang; Yu Ye; Deping Song; Lingbao Kong; Jinghua Zhang; et al. (Virus Genes, 2020)

Multiple Xanthomonas campestris pv. campestris 8004 type III effectors inhibit immunity induced by flg22 - Yan Huang; Tongqi Li; Ting Xu; Zizhong Tang; Jingya Guo; Yi Cai (Planta, 2020)

Pan-genome analysis of Paenibacillus polymyxa strains reveals the mechanism of plant growth promotion and biocontrol - Liangliang Zhou; Ting Zhang; Shan Tang; Xueqin Fu; Shuijing Yu (Antonie van Leeuwenhoek, 2020)

Correction to: Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Optimal error analysis of MJO prediction associated with uncertainties in sea surface temperature over Indian Ocean - Xiaojing Li; Youmin Tang; Lei Zhou; Zhixiong Yao; Zheqi Shen; Junde Li; Ting Liu (Climate Dynamics, 2020)
In this study, the predictability of the Madden–Julian Oscillation (MJO) is investigated using the coupled Community Earth System Model (CESM) and the climatically relevant singular vector (CSV) method. The CSV method is an ensemble-based strategy to calculate the optimal growth of the initial error on the climate scale. We focus on the CSV analysis of MJO initialized at phase II, facilitating the investigation of the effect of the initial errors of the sea surface temperature (SST) in the Indian Ocean on it. Six different MJO events are chosen as the study cases to ensure the robustness of the results. The results indicate that for all the study cases, the optimal perturbation structure of the SST, denoted by the leading mode of the singular vectors (SVs), is a meridional dipole-like pattern between the Bay of Bengal and the southern central Indian Ocean. The MJO signal tends to be more converged and significant in the Eastern Hemisphere while the model is perturbed by leading SV. The moist static energy analysis results indicate that the eastward propagation is much more evident in the terms of vertical advection and radiation flux than others. Therefore, the SV perturbation can strengthen and converge the MJO signal mostly by increasing the vertical advection of the moist static energy. Further, the sensitivity studies indicate that the structure of the leading SV is not sensitive to the initial states, which suggests that we might not need to calculate SVs for each initial time in constructing the ensemble prediction, significantly saving computational time in the operational forecast systems.

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

BRAFi induced demethylation of miR-152-5p regulates phenotype switching by targeting TXNIP in cutaneous melanoma - Kezhu Li; Mingrui Tang; Shuang Tong; Chenchao Wang; Qiang Sun; Mengzhu Lv; Xu Sun; Ting Wang; Shifeng Jin (Apoptosis, 2020)

High Canonical Wnt/β-Catenin Activity Sensitizes Murine Hematopoietic Stem and Progenitor Cells to DNA Damage - Yiting Wang; Hui Cui; Si Tao; Ting Zeng; Jianying Wu; Zhendong Tao; Liu Zhang; Bing Zou; Zhiyang Chen; George B. Garside; Duozhuang Tang (Stem Cell Reviews and Reports, 2020)
Aging is characterized by the accumulation of DNA damage and a decrease in stem cell functionality, yet molecular mechanisms that limit the maintenance of stem cells in response to DNA damage remain to be delineated. Here we show in mouse models that DNA damage leads to a transient over-activation of Wnt signaling in hematopoietic stem cells (HSCs), and that high activity of canonical Wnt/β-catenin signaling sensitizes HSCs to DNA damage induced by X-irradiation which results in preferential maintenance of HSCs with low levels of Wnt signaling. The study shows that genetic or chemical activation of canonical Wnt signaling enhances radiosensitivity of HSCs while inhibition of Wnt signaling decreases it. Together, these results indicate that levels of Wnt signaling activity mediate heterogeneity in the sensitivity of HSCs to DNA damage induced depletion. These findings could be relevant for molecular alterations and selection of stem cells in the context of DNA damage accumulation during aging and cancer formation.

Fungal endophytic communities of two wild Rosa varieties and the role of an endophytic Seimatosporium sp. in enhancing host plant powdery mildew resistance - Yi Zhao; Xiu-ling Ji; Ting Shen; Wen-ting Tang; Shao-shi Li; Zheng-qing Zhu; Jitendra Kumar; Hai-yan Li (Plant and Soil, 2020)

Removal performance and mechanisms of Cr(VI) by an in-situ self-improvement of mesoporous biochar derived from chicken bone - Ting Yang; Caiyun Han; Jie Tang; Yongming Luo (Environmental Science and Pollution Research, 2020)

Recent progress in the structure of glycogen serving as a durable energy reserve in bacteria - Liang Wang; Mengmeng Wang; Michael J. Wise; Qinghua Liu; Ting Yang; Zuobin Zhu; Chengcheng Li; Xinle Tan; Daoquan Tang; Wei Wang (World Journal of Microbiology and Biotechnology, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Reduced Cd, Pb, and As accumulation in rice (Oryza sativa L.) by a combined amendment of calcium sulfate and ferric oxide - Weiwei Zhai; Wenliang Zhao; Honghong Yuan; Ting Guo; Muhammad Zaffar Hashmi; Xingmei Liu; Xianjin Tang (Environmental Science and Pollution Research, 2020)

Phosphate-Solubilizing Pseudomonas sp. Strain P34-L Promotes Wheat Growth by Colonizing the Wheat Rhizosphere and Improving the Wheat Root System and Soil Phosphorus Nutritional Status - Xixi Liu; Xiaoxun Jiang; Xiangyi He; Weirong Zhao; Yuanyuan Cao; Tingting Guo; Ting Li; Haiting Ni; Xinyun Tang (Journal of Plant Growth Regulation, 2019)

Direct Z-scheme La1-xCexMnO3 catalyst for photothermal degradation of toluene - Yiran Tang; Yuwei Tao; Ting Zhou; Baozhu Yang; Qing Wang; Zerui Zhu; Aijuan Xie; Shiping Luo; Chao Yao; Xiazhang Li (Environmental Science and Pollution Research, 2019)

The relationship among probabilistic, deterministic and potential skills in predicting the ENSO for the past 161 years - Ting Liu; Youmin Tang; Dejian Yang; Yanjie Cheng; Xunshu Song; Zhaolu Hou; Zheqi Shen; Yanqiu Gao; Yanling Wu; Xiaojing Li; Banglin Zhang (Climate Dynamics, 2019)
Here, we explored in depth the relationship among the deterministic prediction skill, the probabilistic prediction skill and the potential predictability. This was achieved by theoretical analyses and, in particular, by an analysis of long-term ensemble ENSO hindcast over 161 years from 1856 to 2016. First, a nonlinear monotonic relationship between the deterministic prediction skill and the probabilistic prediction skill, derived by theoretical analysis, was examined and validated using the ensemble hindcast. Further, the co-variability between the potential predictability and the deterministic prediction skill was explored in both perfect model assumption and actual model scenario. On these bases, we investigated the relationship between the potential predictability and probabilistic prediction skill from both the practice of ENSO forecast and theoretical perspective. The results of the study indicate that there are nonlinear monotonic relationships among these three kinds of measures. The potential predictability is considered to be a good indicator for the actual prediction skill in terms of both the deterministic measures and the probabilistic framework. The relationships identified here exhibit considerable significant practical sense to conduct predictability researches, which provide an inexpensive and moderate approach for inquiring prediction uncertainties without the requirement of costly ensemble experiments.

Correction to: Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)
In the original publication of the article, the alphabets in figures were published in upper case and mismatched with the figure legends. The corrected figures and figure legends are given in this Correction.

Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)

Assessment of ECMWF reanalysis data in complex terrain: Can the CERA‐20C and ERA‐Interim data sets replicate the variation in surface air temperatures over Sichuan, China? - Haolin Luo; Fei Ge; Kangquan Yang; Shoupeng Zhu; Ting Peng; Wenyue Cai; Xiaoran Liu; Weiwei Tang (International Journal of Climatology, 2019)
Surface air temperatures (SATs) derived from the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim and CERA‐20C reanalysis data sets are compared with data from 43 observation stations in Sichuan for 1979–2010. The results show (a) the temperatures from the ERA‐Interim and CERA‐20C data sets are strongly correlated with those from the observation stations, although significant cold biases are seen on both annual and seasonal timescales. (b) The biases in SATs are predominately influenced by the differences between the actual topography and the topography used in the reanalysis models. Larger differences in temperature are observed in the plateau and mountainous regions of Sichuan. We confirmed larger SAT biases at high altitudes by categorizing the elevation into four bands, each with a spacing of 1,000 m. (c) We reduced the biases resulting from elevation by using an elevation correction method with internal lapse rates derived from different reanalysis pressure levels. The annual mean bias was reduced from −2.86 to −0.75°C for the ERA‐Interim data set and from −5.27 to −2.21°C for the CERA‐20C data set. After calibration, the correlation coefficients between the difference in SAT (observed minus reanalysis data) and the difference in elevation (station elevation minus model elevation) decreased from −0.97 and −0.91 to −0.29 and −0.30 for the ERA‐Interim and CERA‐20C data sets, respectively. These significant differences should not be ignored in the application of reanalysis data sets to climate research. The evaluation and calibration of reanalysis data sets are essential before making assessments of regional climate change, especially over regions with complex topography.

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Inhibition of JAK2/STAT3 signaling pathway protects mice from the DDP-induced acute kidney injury in lung cancer - Lei Zhang; Peng Lu; Xu Guo; Ting Liu; Xu Luo; Yi-Tang Zhu (Inflammation Research, 2019)

Crystal Transformation of β-CD-MOF Facilitates Loading of Dimercaptosuccinic Acid - Yuehuai Xiong; Li Wu; Tao Guo; Caifen Wang; Wenting Wu; Yan Tang; Ting Xiong; Yong Zhou; Weifeng Zhu; Jiwen Zhang (AAPS PharmSciTech, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Design and application of structural health monitoring system in long-span cable-membrane structure - Teng Tang; Dong-Hui Yang; Lei Wang; Jian-Ren Zhang; Ting-Hua Yi (Earthquake Engineering and Engineering Vibration, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Assessment of trends and variability in surface air temperature on multiple high-resolution datasets over the Indochina Peninsula - Fei Ge; Ting Peng; Klaus Fraedrich; Frank Sielmann; Xiuhua Zhu; Xiefei Zhi; Xiaoran Liu; Weiwei Tang; Pengguo Zhao (Theoretical and Applied Climatology, 2019)

Evaluation of the expression stability of β-actin under bacterial infection in Macrobrachium nipponense - Wen-Yi Geng; Feng-Jiao Yao; Ting Tang; Shan-Shan Shi (Molecular Biology Reports, 2019)

Adsorption characteristics of Cu(II) and Zn(II) by nano-alumina material synthesized by the sol-gel method in batch mode - Ren-yu Wang; Wei Zhang; Li-ying Zhang; Tian Hua; Gang Tang; Xiao-qian Peng; Ming-hui Hao; Qi-ting Zuo (Environmental Science and Pollution Research, 2019)

An intermediate coupled model for the tropical ocean-atmosphere system - Xunshu Song; Dake Chen; Youmin Tang; Ting Liu (Science China Earth Sciences, 2018)

Characterization of the complete chloroplast genome of a critically endangered decaploid rose species, Rosa praelucens (Rosaceae) - Hong-ying Jian; Shu-dong Zhang; Ting Zhang; Xian-qin Qiu; Hui-jun Yan; Shu-bin Li; Qi-gang Wang; Kai-xue Tang (Conservation Genetics Resources, 2018)

Screening of a beta-cypermethrin-degrading bacterial strain Brevibacillus parabrevis BCP-09 and its biochemical degradation pathway - Jie Tang; Bo Liu; Ting-ting Chen; Kai Yao; Lin Zeng; Chao-yi Zeng; Qing Zhang (Biodegradation, 2018)

Detection of Insertions/Deletions Within SIRT1, SIRT2 and SIRT3 Genes and Their Associations with Body Measurement Traits in Cattle - Yunyun Jin; Qing Yang; Jiayang Gao; Qi Tang; Bo Duan; Ting Yu; Xinglei Qi; Jiming Liu; Rongmin Wang; Ruihua Dang; Chuzhao Lei; Hong Chen; et al. (Biochemical Genetics, 2018)

Nitrogen additions reduce rhizospheric and heterotrophic respiration in a subtropical evergreen broad-leaved forest - Yong Peng; Guan-tao Chen; Shun Li; Hong-ling Hu; Ting-xing Hu; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2018)

Effect of early fluid resuscitation combined with low dose cyclophosphamide on intestinal barrier function in severe sepsis rats - Su-Yu Tang; Shun-Wen Zhang; Jie Zhang; Jiang-Tao Dong; Jiang-Dong Wu; Peng Guo; Jun-Ting Yang; Wan-Jiang Zhang; Fang Wu (Drug Delivery and Translational Research, 2018)

MLKL mediates apoptosis via a mutual regulation with PERK/eIF2α pathway in response to reactive oxygen species generation - Wen-Xiang Cao; Ting Li; Zheng-Hai Tang; Le-Le Zhang; Zhao-Yu Wang; Xia Guo; Min-Xia Su; Xiuping Chen; Jin-Jian Lu (Apoptosis, 2018)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Primary culture of cat intestinal epithelial cells in vitro and the cDNA library construction - Gui hua Zhao; Ye Liu; Yun tang Cheng; Qing song Zhao; Xiao Qiu; Chao Xu; Ting Xiao; Song Zhu; Gong zhen Liu; Kun Yin (Acta Parasitologica, 2018)
Felids are the only definitive hosts of Toxoplasma gondii . To lay a foundation for screening the T . gondii -felids interaction factors, we have developed a reproducible primary culture method for cat intestinal epithelial cells (IECs). The primary IECs were isolated from a new born cat’s small intestine jejunum region without food ingress, and respectively in vitro cultured by tissue cultivation and combined digestion method with collagenase XI and dispase I, then purified by trypsinization. After identification, the ds cDNA of cat IECs was synthesized for constructing pGADT7 homogenization three-frame plasmid, and transformed into the yeast Y187 for generating the cDNA library. Our results indicated that cultivation of primary cat IECs relays on combined digestion to form polarized and confluent monolayers within 3 days with typical features of normal epithelial cells. The purified cells cultured by digestion method were identified to be nature intestinal epithelial cells using immunohistochemical analysis and were able to maintain viability for at least 15 passages. The homogenizable ds cDNA, which is synthesized from the total RNA extracted from our cultured IECs, distributed among 0.5–2.0 kb, and generated satisfying three-frame cDNA library with the capacity of 1.2 × 10 6 and the titer of 5.2 × 10 7 pfu/mL. Our results established an optimal method for the culturing and passage of cat IECs model in vitro , and laid a cDNA library foundation for the subsequent interaction factors screening by yeast two-hybrid.

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Determination of the potential implementation impact of 2016 ministry of environmental protection generic assessment criteria for potentially contaminated sites in China - Yuanyuan Cheng; Yu-Ting Tang; C. Paul Nathanail (Environmental Geochemistry and Health, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Complexation of sulfamethazine with Cd(II) and Pb(II): implication for co-adsorption of SMT and Cd(II) on goethite - Ting Tang; Chen Yang; Li Wang; Xianying Jiang; Zhi Dang; Weilin Huang (Environmental Science and Pollution Research, 2018)

Terpenoids from Vitex trifolia and their anti-inflammatory activities - Fengyan Bao; Ruotian Tang; Li Cheng; Cuiyun Zhang; Chongyue Qiu; Ting Yuan; Lihan Zhu; Hua Li; Lixia Chen (Journal of Natural Medicines, 2018)

The occurrence of rust disease, and biochemical and physiological responses on Apocynum venetum plants grown at four soil water contents, following inoculation with Melampsora apocyni - Peng Gao; Ting-Yu Duan; Michael J. Christensen; Zhi-Biao Nan; Qi-Tang Liu; Fan-Jie Meng; Jing-Feng Huang (European Journal of Plant Pathology, 2018)

Photodegradation of Scopoletin in Organic Solvents and Aqueous Solutions: Kinetics and Degradation Pathways - Jinxiang Luo; Lizhi Tang; Yongqiang Zhang; Wei Ding; Ting Lai (Water, Air, & Soil Pollution, 2018)

Actionable secondary findings from whole-genome sequencing of 954 East Asians - Clara Sze-man Tang; Saloni Dattani; Man-ting So; Stacey S. Cherny; Paul K. H. Tam; Pak C. Sham; Maria-Mercè Garcia-Barcelo (Human Genetics, 2018)

Kinetics and pathways of Bezafibrate degradation in UV/chlorine process - Xue-Ting Shi; Yong-Ze Liu; Yu-Qing Tang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

CRISPR/Cas9-mediated multiple single guide RNAs potently abrogate pseudorabies virus replication - Yan-Dong Tang; Ji-Ting Liu; Tong-Yun Wang; Ming-Xia Sun; Zhi-Jun Tian; Xue-Hui Cai (Archives of Virology, 2017)

Design, synthesis and biological evaluation of urea-based benzamides derivatives as HDAC inhibitors - Yong Zhu; Xin Chen; Ting Ran; Jiaqi Niu; Shuang Zhao; Tao Lu; Weifang Tang (Medicinal Chemistry Research, 2017)

Serum Copeptin Predicts Severity and Recurrent Stroke in Ischemic Stroke Patients - Wan-Zhong Tang; Xiao-Bo Wang; Huan-Ting Li; Mei Dong; Xiang Ji (Neurotoxicity Research, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

CADASIL mutant NOTCH3(R90C) decreases the viability of HS683 oligodendrocytes via apoptosis - Mibo Tang; Changhe Shi; Bo Song; Jing Yang; Ting Yang; Chengyuan Mao; Yusheng Li; Xinjing Liu; Shuyu Zhang; Hui Wang; Haiyang Luo; Yuming Xu (Molecular Biology Reports, 2017)

Effects of short-term high temperature on grain quality and starch granules of rice (Oryza sativa L.) at post-anthesis stage - Jianlin Chen; Liang Tang; Peihua Shi; Baohua Yang; Ting Sun; Weixing Cao; Yan Zhu (Protoplasma, 2017)

Effect of nitrogen additions on root morphology and chemistry in a subtropical bamboo forest - Guan-tao Chen; Li-hua Tu; Yong Peng; Hong-ling Hu; Ting-xing Hu; Zhen-feng Xu; Li Liu; Yi Tang (Plant and Soil, 2017)

Effects of short-term post-anthesis high-temperature stress on dynamic process of accumulation of grain protein and its composition in rice (Oryza sativa L.) - Jianlin Chen; Liang Tang; Peihua Shi; Baohua Yang; Ting Sun; Weixing Cao; Yan Zhu (Brazilian Journal of Botany, 2017)

Di-2-ethylhexyl phthalate induced oxidative damage involving FasL-associated apoptotic pathway in mouse spermatogenic GC-2spd cells - Xiao Tang; Kun Tong; Lishan Zhu; Guoqing Fu; Wei Chang; Ting Zhou; Zhibing Zhang; Ling Tong; Ling Zhang; Yuqin Shi (Molecular & Cellular Toxicology, 2016)

Phytochemistry and pharmacological activities of Vaccaria hispanica (Miller) Rauschert: a review - Guohong Zhou; Liying Tang; Ting Wang; Xidan Zhou; Zhenzhen Kou; Jing Wu; Zhuju Wang (Phytochemistry Reviews, 2016)

Inverse Expression Levels of EphrinA3 and EphrinA5 Contribute to Dopaminergic Differentiation of Human SH-SY5Y Cells - Ting Wang; Jing Chen; Chuan-Xi Tang; Xiao-Yan Zhou; Dian-Shuai Gao (Journal of Molecular Neuroscience, 2016)

Effect of Rhizophagus irregularis on osmotic adjustment, antioxidation and aquaporin PIP genes expression of Populus × canadensis ‘Neva’ under drought stress - Ting Liu; Zhen Li; Chen Hui; Ming Tang; Haoqiang Zhang (Acta Physiologiae Plantarum, 2016)

Facile microwave-assisted synthesis of benzimidazole scaffolds via Ugi-type three-component condensation (3CC) reactions - Gui-Ting Song; Zhi-Gang Xu; Dian-Yong Tang; Shi-Qiang Li; Zhi-Gang Xie; Hong-Liang Zhong; Zhi-Wei Yang; Jin Zhu; Jin Zhang; Zhong-Zhu Chen (Molecular Diversity, 2016)

GOLPH3 Mediated Golgi Stress Response in Modulating N2A Cell Death upon Oxygen-Glucose Deprivation and Reoxygenation Injury - Ting Li; Hong You; Xiaoye Mo; Wenfang He; Xiangqi Tang; Zheng Jiang; Shiyu Chen; Yang Chen; Jie Zhang; Zhiping Hu (Molecular Neurobiology, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Effect of Boric Acid Supplementation on the Expression of BDNF in African Ostrich Chick Brain - Juan Tang; Xing-ting Zheng; Ke Xiao; Kun-lun Wang; Jing Wang; Yun-xiao Wang; Ke Wang; Wei Wang; Shun Lu; Ke-li Yang; Peng-Peng Sun; Haseeb Khaliq; et al. (Biological Trace Element Research, 2016)

Opium poppy mosaic virus, a new umbravirus isolated from Papaver somniferum in New Zealand - Joe Tang; Bénédicte Lebas; Lia Liefting; Stella Veerakone; Ting Wei; Lisa Ward (Archives of Virology, 2016)

Damped oscillations in a multiple delayed feedback NF- $$κ$$ κ B signaling module - Wen-Ting Yu; Jun Tang; Jun Ma; Jin-Ming Luo; Xian-Qing Yang (European Biophysics Journal, 2015)

Simulating evolution of a loess gully head with cellular automata - Xiaojing Liu; Guo’an Tang; Jianyi Yang; Zhou Shen; Ting Pan (Chinese Geographical Science, 2015)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Culture temperature modulates monoclonal antibody charge variation distribution in Chinese hamster ovary cell cultures - Xintao Zhang; Ya-Ting Sun; Hongping Tang; Li Fan; Dongdong Hu; Jintao Liu; Xuping Liu; Wen-Song Tan (Biotechnology Letters, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Cisplatin combined with hyperthermia kills HepG2 cells in intraoperative blood salvage but preserves the function of erythrocytes - Jin-ting Yang; Li-hui Tang; Yun-qing Liu; Yin Wang; Lie-ju Wang; Feng-jiang Zhang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2015)

Direct and indirect effects of nitrogen additions on fine root decomposition in a subtropical bamboo forest - Li-hua Tu; Yong Peng; Gang Chen; Hong-ling Hu; Yin-long Xiao; Ting-xing Hu; Li Liu; Yi Tang (Plant and Soil, 2015)

Critical Role of Tet3 in Neural Progenitor Cell Maintenance and Terminal Differentiation - Ting Li; Dehua Yang; Jia Li; Yu Tang; Juan Yang; Weidong Le (Molecular Neurobiology, 2015)

Application of multiscale entropy in arterial waveform contour analysis in healthy and diabetic subjects - An-Bang Liu; Hsien-Tsai Wu; Chun-Wei Liu; Cyuan-Cin Liu; Chieh-Ju Tang; I-Ting Tsai; Cheuk-Kwan Sun (Medical & Biological Engineering & Computing, 2015)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Erratum to: RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2014)

Effects of arbuscular mycorrhizal colonization on the biomass and bioenergy production of Populus × canadensis ‘Neva’ in sterilized and unsterilized soil - Ting Liu; Chunyan Wang; Hui Chen; Fengru Fang; Xiaoqin Zhu; Ming Tang (Acta Physiologiae Plantarum, 2014)

Development and characterization of sixteen microsatellite primers in Abies chensiensis and A. fargesii (Pinaceae) - Ting Zhan; Qi-Wei Zhang; Xie Wang; Shao-Qing Tang (Conservation Genetics Resources, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Genetic structure of rice black-streaked dwarf virus populations in China - Xiao Yin; Fang-Qiang Zheng; Wei Tang; Qin-Qin Zhu; Xiang-Dong Li; Guang-Min Zhang; Huan-Ting Liu; Bao-Shen Liu (Archives of Virology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Advances in monoclonal antibody application in myocarditis - Li-na Han; Shuang He; Yu-tang Wang; Li-ming Yang; Si-yu Liu; Ting Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Factors associated with decision time for patients with ST-segment elevation acute myocardial infarction - Lu Qian; Kang-ting Ji; Jin-liang Nan; Qin Lu; Yong-jin Zhu; Lu-ping Wang; Lian-ming Liao; Ji-fei Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of histamine on spontaneous neuropathic pain induced by peripheral axotomy - Jie Yu; Guo-Dong Lou; Jia-Xing Yue; Ying-Ying Tang; Wei-Wei Hou; Wen-Ting Shou; Hiroshi Ohtsu; Shi-Hong Zhang; Zhong Chen (Neuroscience Bulletin, 2013)

Dynamic mechanism and present situation of rural settlement evolution in China - Guohua Zhou; Yanhua He; Chengli Tang; Tao Yu; Guozhen Xiao; Ting Zhong (Journal of Geographical Sciences, 2013)

A gain-of-function mutation in IAA8 alters Arabidopsis floral organ development by change of jasmonic acid level - Jing Wang; Da-Wei Yan; Ting-Ting Yuan; Xiang Gao; Ying-Tang Lu (Plant Molecular Biology, 2013)

RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Karyological diversity of wild Rosa in Yunnan, southwestern China - Hong Ying Jian; Ting Zhang; Qi Gang Wang; Shu Bin Li; Hao Zhang; Kai Xue Tang (Genetic Resources and Crop Evolution, 2013)

Dominantly Inherited Myotonia Congenita Resulting from a Mutation That Increases Open Probability of the Muscle Chloride Channel CLC-1 - David P. Richman; Yawei Yu; Ting-Ting Lee; Pang-Yen Tseng; Wei-Ping Yu; Ricardo A. Maselli; Chih-Yung Tang; Tsung-Yu Chen (NeuroMolecular Medicine, 2012)

Tetrandrine citrate eliminates imatinib-resistant chronic myeloid leukemia cells in vitro and in vivo by inhibiting Bcr-Abl/β-catenin axis - Xiao-hua Xu; Yi-chao Gan; Gen-bo Xu; Ting Chen; Hong Zhou; Jin-fen Tang; Ying Gu; Fei Xu; Ying-ying Xie; Xiao-ying Zhao; Rong-zhen Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Constitutive activation of STAT3 is predictive of poor prognosis in human gastric cancer - Hua Xiong; Wan Du; Ji-Lin Wang; Ying-Chao Wang; Jie-Ting Tang; Jie Hong; Jing-Yuan Fang (Journal of Molecular Medicine, 2012)

Enhancement of butanol production and reducing power using a two-stage controlled-pH strategy in batch culture of Clostridium acetobutylicum XY16 - Ting Guo; Baijun Sun; Min Jiang; Hao Wu; Tengfei Du; Yan Tang; Ping Wei; Pingkai Ouyang (World Journal of Microbiology and Biotechnology, 2012)

Transcriptomic analysis of the housefly (Musca domestica) larva using massively parallel pyrosequencing - Fengsong Liu; Ting Tang; Lingling Sun; T. A. Jose Priya (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Typhoon-Ocean Interaction in the Western North Pacific: Part 2 - IamFei Pun; Ya-Ting Chang; I.I. Lin; Tswen Yung Tang; Ren-Chieh Lien (Oceanography, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

c-Myc influences olaquindox-induced apoptosis in human hepatoma G2 cells - Ting Zhang; Shu-Sheng Tang; Xi Jin; Feng-Ying Liu; Chao-Ming Zhang; Wen-Xia Zhao; Shen Zhang; Chun-Di Sun; Xi-Long Xiao (Molecular and Cellular Biochemistry, 2011)

Fluorofenidone attenuates renal interstitial fibrosis in the rat model of obstructive nephropathy - Bing-xin Li; Yi-ting Tang; Wei Wang; Yan-yun Xie; Na-sui Wang; Qiong-jing Yuan; Fang-fang Zhang; Zhang-zhe Peng; Gao-yun Hu; Li-jian Tao (Molecular and Cellular Biochemistry, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Examining Local Coastal Zone Management Capacity in U.S. Pacific Coastal Counties - Zhenghong Tang; Michael K. Lindell; Carla Prater; Ting Wei; Christopher M. Hussey (Coastal Management, 2011)

Enhanced biodesulfurization by magnetic immobilized Rhodococcus erythropolis LSSE8-1-vgb assembled with nano-γ-Al2O3 - Ting Zhang; Wang-Liang Li; Xiao-Xin Chen; Huang Tang; Qiang Li; Jian-Min Xing; Hui-Zhou Liu (World Journal of Microbiology and Biotechnology, 2011)

A young and booming approach: the extreme lateral supracerebellar infratentorial approach - Xin Chen; Yu-Gong Feng; Wan-Zhong Tang; Huan-Ting Li; Zhao-Jian Li (Neuroscience Bulletin, 2010)

Simultaneous Determination of Xanthopterin and Isoxanthopterin in Human Urine by Synchronous Fluorescence Spectroscopy - Yi-Qun Wan; Li-Juan Tang; Ting Tan (Journal of Fluorescence, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Novel 1-alkyl-tryptophan derivatives downregulate IDO1 and IDO2 mRNA expression induced by interferon-gamma in dendritic cells - Ting Sun; Xiang-Hua Chen; Zheng-De Tang; Jiong Cai; Xiao-Yan Wang; Shih-Chen Wang; Zhao-Long Li (Molecular and Cellular Biochemistry, 2010)

Danshen protects endothelial progenitor cells from oxidized low-density lipoprotein induced impairment - Kang-ting Ji; Jun-de Chai; Cheng Xing; Jin-liang Nan; Peng-lin Yang; Ji-fei Tang (Journal of Zhejiang University-SCIENCE B, 2010)

Cold deep water in the South China Sea - Ya-Ting Chang; Wei-Lun Hsu; Jen-Hua Tai; Tswen Yung Tang; Ming-Huei Chang; Shenn-Yu Chao (Journal of Oceanography, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Characterization of hydrangea chlorotic mottle virus, a new member of the genus Carlavirus - Joe Tang; Scott J. Harper; Ting Wei; Gerard R. G. Clover (Archives of Virology, 2010)

Snowfall trends and variability in Qinghai, China - Chang-Qing Ke; Ting Yu; Kan Yu; Guo-Dong Tang; Lorenz King (Theoretical and Applied Climatology, 2009)

Epigallocatechin-3-gallate induced primary cultures of rat hippocampal neurons death linked to calcium overload and oxidative stress - Shu-Ting Yin; Ming-Liang Tang; Hong-Min Deng; Tai-Ran Xing; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Opposite effects of α-lipoic acid on antioxidation and long-term potentiation in control and chronically lead-exposed rats - Hui-Li Wang; Xiang-Tao Chen; Shu-Ting Yin; Jin Liu; Ming-Liang Tang; Chuan-Yun Wu; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Effects of pcDNA3-β-NGF Gene-modified BMSC on the Rat Model of Parkinson’s Disease - Ting-Hua Wang; Zhong-Tang Feng; Peng Wei; Hui Li; Zhen-Jiang Shi; Li-Yan Li (Journal of Molecular Neuroscience, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Simulation on slope uncertainty derived from DEMs at different resolution levels: a case study in the Loess Plateau - Tang Guoan; Zhao Mudan; Li Tianwen; Liu Yongmei; Zhang Ting (Journal of Geographical Sciences, 2003)

Diversity associated with the second expressed H L A - D R B locus in the human population - FuMeei Robbins; Carolyn Katovich Hurley; Ting Tang; Hanlong Yao; Y. S. Lin; Judy Wade; Nancy Goeken; Robert J. Hartzman (Immunogenetics, 1997)